Unraveling social-ecological vulnerability in small-scale farming through causal loop modeling - Bárbara Chávez; Marcelo D. Miranda; Camilo Oyarzo; Paulina Rodriguez-Díaz; Santiago Kaulen; Julián Caviedes; José Tomás Ibarra; Carla Marchant (Agricultural Systems, 2026)

The effectiveness of urban green space management on butterfly diversity depends on the species functional groups - Yolanda Melero; Marc Riera; Juan D. Rodriguez; Joan Pino (Urban Forestry & Urban Greening, 2026)

Release of bound steroid from the androgen and estrogen receptors is induced by DDT and its analogs - Matthew D. Rosales; Tahyra Soto; Jacqueline I. Goodship; Ahyssa R. Cruz; Isaac A. Rodriguez; Ventura Cuba Flores; Amanda Chavez; Monica P. Solis; Esmeralda Lopez; Frank B. Dean; Evangelia Kotsikorou (Toxicology and Applied Pharmacology, 2026)

Multiscale experimental–numerical study of alkali-free SP flooding with sensitivity analysis in a venezuelan extra-heavy oil reservoir - A. Askarova; H. Imran; F. Rodriguez; H. Belhaj; D. Dorhjie; A. Bello; C. Yuan; C. Bejarano; R. Morales; A. Cheremisin (Fuel, 2026)

Examining widely held propositions on human dietary protein needs and benefits: a critical review of the science that shapes both the data and our understanding of an essential macronutrient - Mitchell M. Kanter; Sally Aaron; Steven N. Austad; Andrew W. Brown; Nicholas A. Burd; Wayne W. Campbell; Mark Cope; Teresa A. Davis; John W. Erdman; Miguel Freitas; Kristen Hicks-Roof; Samuel Klein; et al. (Critical Reviews in Food Science and Nutrition, 2026)

Lake sediment records of deglaciation and post-glacial paleoenvironmental conditions, northeast Pennsylvania, USA - Matthew S. Finkenbinder; Timothy P. Lane; Kathryn R. Adamson; Bruce P. Finney; Mark B. Abbott; Alistair J. Monteath; Adam Ianno; Cassandra N. Papp; Angus F. Fortune; Michael J. Delpais; Megan E. Novak; Angelica Y. Delgado Rodriguez; et al. (Quaternary Science Reviews, 2026)

GollumFit: An icecube open-source framework for binned-likelihood neutrino telescope analyses - R. Abbasi; M. Ackermann; J. Adams; S.K. Agarwalla; J.A. Aguilar; M. Ahlers; J.M. Alameddine; N.M. Amin; K. Andeen; C. Argüelles; Y. Ashida; S. Athanasiadou; et al. (Computer Physics Communications, 2026)

Electronic structure engineering of 2D Ni-MOF/CNTs for glucose monitoring and energy supply in a wearable sweat sensor system - Rui-Dong Shi; Guo-Tao Xiang; Tao Cheng; Zi-Dong Zhou; Na Chen; Raul D. Rodriguez; Jin-Ju Chen (Chemical Engineering Journal, 2026)

Prevalent detection of multiclass environmental chemicals in paired CSF and plasma samples and their potential associations with postpartum depressive symptoms in pregnant women - Bushra Amreen; Corina Lesseur; Ravikumar Jagani; Hiraj Patel; Daniel Katz; Joshua Hamburger; Noel Strong; Leah Habersham; Anna-Sophie Rommel; Lotje D. de Witte; Chris Gennings; M Mercedes Perez-Rodriguez; et al. (Environmental Research, 2026)

On the Possibility of Ionospheric Memory Over the Low-Latitude Mexican Region - M. A. Sergeeva; I. D. Orrala-Legorreta; E. Rodriguez-Orozco; J. H. Castro-Chacon; O. A. Maltseva; J. A. Gonzalez-Esparza; P. Corona-Romero; V. J. Gatica-Acevedo; M. Pazos; M. E. Gonzalez-Alvarez; R. Bonifaz; A. Melgarejo-Morales; et al. (Pure and Applied Geophysics, 2026)
Features of possible regional ionospheric memory manifested themselves at low-latitudes under solar eclipse conditions.

Reliability of M-wave amplitude measurement from paired stimulations across different muscle groups before and after submaximal contraction to failure - C. Lanfranchi; D. Neyroud; J. Rodriguez-Falces; N. Place (European Journal of Applied Physiology, 2026)

Beyond Coverage: A Systematic Review and Thematic Analysis of Delivery, Compliance, Equity and Impact in Mass Deworming for Soil-Transmitted Helminths - Harley M. Rodriguez; Angelica Marie B. Rostata; Jan Joseph Rainer Christorey Maria Salgado; Timothy Liam D. Rivera; Jose Ma. M. Angeles (Acta Parasitologica, 2026)

Confirmed Outbreaks of Streptococcosis Caused by Streptococcus agalactiae Serotype Ia in Nile Tilapia Culture From Campeche, Mexico - R. A. Avila‐Castillo; R. E. del Rio‐Rodriguez; S. A. Soto‐Rodriguez; J. Navarro‐Flores; A. D. Cu‐Escamilla; F. I. Marrujo‐Lopez; K. G. Aguilar‐Rendon; M. I. Gomez‐Solano (Journal of Fish Diseases, 2026)
Streptococcus agalactiae was confirmed as the etiologic agent of streptococcosis in Nile tilapia ( Oreochromis niloticus ) from Campeche, Mexico, during a cross‐sectional investigation of eight semi‐intensive farms (2021–2022) that yielded virulent strains in a challenge assay. Standard bacteriology, histopathology, API‐20 Strep phenotyping, one‐step PCR, and real‐time PCR confirmed S. agalactiae in five farms (62.5%). Gross and histological lesions were characterised by mid‐axial and peduncular muscle abscesses, extensive myonecrosis, granuloma formation, polyserositis, and occasional suppurative meningitis. Experimental infections fulfilled Koch's postulates. Juveniles of O. niloticus (20 g) infected with strain ASG‐2290 at 10 6 CFU/mL produced 53% mortality at 96 h. Whole‐genome sequencing of the strains ASG‐2290 and ASG‐2292 identified them as S. agalactiae Ia, marking the first report of this serotype isolated from farmed tilapia in Mexico. Frequent interstate fry movements are likely to be a risk factor for pathogen dissemination. These findings document the geographic expansion of pathogenic S. agalactiae into the Yucatan Peninsula, underscoring the need for strengthened surveillance, biosecurity, and diagnostic capacity to mitigate economic losses in Mexican tilapia aquaculture. Considering that tilapia aquaculture is carried out all year‐round in the Yucatan Peninsula, the implications of these findings are of major concern.

Advancing Coronary Risk Assessment Through Combined Radiomic, Mechanical, and Hemodynamic Analysis - Anna Corti; Marco Stefanati; Vittorio Lissoni; Matteo Leccardi; Francesco Bruno; Alessandro Depaoli; Pietro Cerveri; Francesco Migliavacca; Valentina D. A. Corino; José F. Rodriguez Matas; Luca Mainardi; Gabriele Dubini (Annals of Biomedical Engineering, 2026)
Purpose Detecting vulnerable coronary plaques through coronary computed tomography angiography (CCTA) is a crucial, yet challenging task. To date, most of the proposed vulnerability markers have been studied in isolation. This study introduces the first integrated analysis combining radiomic, mechanical, and hemodynamic factors to explore their synergistic contribution to plaque vulnerability. Methods The study analyzed 161 plaques in 46 coronary arteries from 39 patients, with 7 arteries (28 plaques) from 7 individuals, labeled as vulnerable from intravascular imaging. First, CCTA radiomic features were extracted. Second, mechanical markers were computed through finite element simulations conducted with varying material characteristics, accounting for the arterial wall mechanical properties’ uncertainties. Third, hemodynamic markers were derived from transient computational fluid dynamics simulations. Finally, a machine learning pipeline was developed to classify coronary arteries and patients based on radiomic, mechanical, and hemodynamic features, both individually and in combination. Results Radiomics achieved the highest sensitivity (1.00), with all vulnerable patients identified, but lower specificity (0.69). Differently, mechanics and hemodynamics achieved higher specificities (0.94 and 0.97, respectively) but lower sensitivities (both 0.86). By integrating at least two out of the three models, the predictive performance improved, up to sensitivity = 1.00 and specificity = 0.97, with only one misclassified case. Conclusion Although based on only 39 patients, the results highlight the power of a multi-level integrative approach for coronary plaque assessment. The study revealed that (i) hemodynamics outperformed mechanics and radiomics; (ii) while radiomics maximized sensitivity, mechanics and hemodynamics prioritized specificity, and (iii) integrating at least two variable types added value.

Per- and polyfluoroalkyl substances and pesticides in black bears (Ursus americanus) and grizzly bears (Ursus arctos horribilis) from Montana's Cabinet-Yaak ecosystem: A baseline assessment of emerging and legacy contaminants - Brian C. Balmer; Marina D. Rodriguez; Justin E. Teisberg; Michelle L. Hladik; Wayne F. Kasworm; Amber Kornak; Thomas G. Radandt; Landon M. Keele; Erin L. Pulster (Environmental Pollution, 2026)

Biosynthesized magnesium oxide nanoparticles enhance alfalfa growth by modulating physiological and biochemical processes under field conditions - Rania Nasra; Issam Nouairi; Soumaya Bourgou; Ons Talbi; Ignacio D. Rodriguez-Llorente; Haythem Mhadhbi; Kais Zribi (Biocatalysis and Agricultural Biotechnology, 2026)

Climatic Niche Modelling Reveals Limited Phylogenetic Niche Conservatism in New World Crocodylians - Andrés L. Rodriguez‐Cordero; Nancy E. McIntyre; Richard D. Stevens; Joseph D. Manthey; Carlos Portillo‐Quintero; Natasja Van Gestel; Sergio A. Balaguera‐Reina; Brandon A. Gross; Margaret Munn; Llewellyn D. Densmore (Journal of Biogeography, 2026)
Aim Phylogenetic niche conservatism, the tendency of closely related species to retain ancestral ecological traits, has gained considerable interest, yet the lack of integration across independent evaluation methods has hindered our understanding of whether niches are conserved or dynamic. Such an understanding is especially relevant for taxa of conservation concern, such as crocodylians (order Crocodylia). This study assessed niche conservatism among New World crocodylians by combining ensemble species distribution models, phylogenetics, and standard metrics of geographic and environmental niche overlap. Location America. Major Taxa Order Crocodylia. Methods We estimated species' climatic niches in geographic and environmental dimensions to assess overlap patterns and quantified associations between niche overlap and phylogenetic patristic distance using the Mantel test and phylogenetic independent contrast (PIC). Results Overlap analyses in geographic and environmental spaces revealed climatic niche differentiation across the clade, suggesting divergent environmental preferences among species. The relationship between phylogenetic patristic distance and climatic niche overlap assessed via Mantel tests revealed a significant negative correlation with geographic niche overlap ( ρ = −0.361, p = 0.005), but no evidence for associations with environmental niche overlap (Schoener's D: ρ = −0.079, p = 0.184; Hellinger's I: ρ = −0.063, p = 0.250), suggesting that more distantly related species overlap less geographically. In contrast, the relationship assessed using PIC revealed no evidence for associations between phylogenetic distance and either geographic ( ρ = −0.200, p = 0.579) or environmental niche overlap (D: ρ = −0.294, p = 0.41; I: ρ = −0.319, p = 0.369). Conclusions We found no strong or consistent evidence for phylogenetic conservatism in climatic niches across both geographic (inverse relationship) and environmental (no relationship) dimensions in New World crocodylians. This study enhances our understanding of niche dynamics and highlights the value of integrating niche modelling with phylogenetic analyses to detect biogeographic and evolutionary patterns.

Pheromone trail following is not modulated by previous visit to food location, distance travelled, or travel direction in the ant Lasius niger - L.-A. Poissonnier; D. Winter; F.‑J. Olivera‑Rodriguez; C. Werneke; T. J. Czaczkes (Insectes Sociaux, 2026)
Ant foraging and recruitment often relies heavily on pheromone trails, and ants modulate pheromone trail deposition strategically. Ants are also known to modulate trail following depending on their own private information, such as the known location of the nest and their knowledge of food sources in the environment. Here we ask how a series of important context variables—distance from the nest, direction of travel, and prior food discovery—affects the fidelity of pheromone trail following in the black garden ant Lasius niger . Using both an open arena assay and a binary Y-maze design, we evaluated whether ants adjust their trail-following behaviour. Ants exhibited robust and consistent trail-following behaviour across all conditions. Surprisingly, we found no significant modulation by distance, travel direction, or recent experience. However, we observed that distance travelled before finding a pheromone trail significantly influenced subsequent walking patterns such as straightness, speed, and total distance travelled. These findings suggest that while L. niger trail-following behaviour is remarkably stable across contexts, locomotory traits remain plastic and context-sensitive. The decoupling of pheromone response from internal or external conditions highlights the need for further investigation into the mechanisms regulating individual foraging decisions in social insects.

Non-Candida fungal cholecystitis - an uncommon occurrence even in the right host - Mitchell G. Dumais; Mary M. Czech; Mustafa A. Hyder; Rachel R. Lee; Juan C. Gea-Banacloche; Christopher G. Kanakry; Sun A. Kim; Bindu Adhikari; Matthew D. Surette; Adrian M. Zelazny; Amir Seyedmousavi; Jennifer M. Cuellar-Rodriguez (European Journal of Clinical Microbiology & Infectious Diseases, 2026)
Invasive fungal infections (IFI) are a significant cause of morbidity and mortality in hematologic malignancy patients and hematopoietic cell transplant (HCT) recipients. Mold cholecystitis has rarely been described. We present a case of disseminated Lomentospora prolificans , that had recrudescence of symptoms with acute cholecystitis. Treatment included a temporary cholecystostomy and administration of the novel antifungal fosmanogepix. At 6 weeks post-HCT, the patient underwent cholecystectomy and completed a course of fosmanogepix, leading to resolution of her infection. Here we review the published literature on non- Candida fungal cholecystitis, underlying risk factors and treatment.

Encapsulation of tyrosinase in liposomes: A biomimetic approach to efficient biodetection of polyphenols in grape juice - Priscila Alessio; Cibely S. Martin; Mateus D. Maximino; Matheus S. Pereira; Constantin Apetrei; Maria L. Rodriguez-Mendez (Journal of Food Engineering, 2026)

Agricultural aerosols may increase the growth of HAB-forming Alexandrium minutum in batch cultures under natural seawater conditions - Richard D. Redil; Isabel Marín-Beltrán; Irene B. Rodriguez (Harmful Algae, 2026)

MFC 5.0: An exascale many-physics flow solver - Benjamin Wilfong; Henry A. Le Berre; Anand Radhakrishnan; Ansh Gupta; Daniel J. Vickers; Diego Vaca-Revelo; Dimitrios Adam; Haocheng Yu; Hyeoksu Lee; Jose Rodolfo Chreim; Mirelys Carcana Barbosa; Yanjun Zhang; et al. (Computer Physics Communications, 2026)

Xylem tissue-inspired sustainable foams from selectively toughened poly(l-lactide)/polycarbonate blends - Anthony V. Tuccitto; Nello D. Sansone; Neelima Tripathi; Rafaela Aguiar; Arturo Rodriguez-Uribe; Amar K. Mohanty; Manjusri Misra; Patrick C. Lee (Chemical Engineering Journal, 2026)

Morphology and particle size distribution in the indoor dust: A hidden threat to human health? - D. Meza-Figueroa; E. Vega; J. Entwistle; A. Angulo-Molina; A. Valencia-Meza; B. Schiavo; V. Rodriguez; B. González-Grijalva; F. Berrellez-Reyes; C. Ortega-Rosas; A. Wellens; A. Namdeo (Environmental Geochemistry and Health, 2026)

Innovative 3D-Image Analysis of Cerebellar Vascularization Highlights Angiogenic Gene Dysregulations in a Murine Model of Apnea of Prematurity - A. Rodriguez-Duboc; C. Racine; M. Basille-Dugay; D. Vaudry; B. Gonzalez; D. Burel (The Cerebellum, 2026)
Apnea of prematurity (AOP) affects 50% of preterm infants causing intermittent hypoxia (IH), which can lead to long-term neurodevelopmental deficits. Cerebellar abnormalities have been observed in AOP but the relationship between vascular alterations and neural development remains unclear. This study investigates how IH affects cerebellar angiogenesis using a murine model of AOP. We developed an innovative 3D imaging workflow combining Imaris and VesselVio software to quantitatively analyze cerebellar vascularization at different postnatal stages (P4, P8, P12, P21, and P70). We correlated these results with a transcriptomic analysis of 23 angiogenesis-related genes in the same stages to uncover the associated molecular pathways. We found that IH induced significant vascular changes, particularly at P4, with a global increase in vascular-network dimensions. By P8, the vascular network normalized, but genes were downregulated in all pathways studied. After P12, at the end of the IH protocol, transcriptional regulations had varied but persisted long-term. Moreover, differential analysis showed distinct effects on superficial versus deep vascular networks, allowing for a more precise understanding of remodeling patterns throughout development. Overall, transcriptomic changes were associated with morphological alterations in a time-dependent manner, suggesting a multiphasic IH response through development with lasting effects. Key regulations included VEGF, angiopoietin, and matrix metalloprotease signaling. These findings demonstrate that IH disrupts cerebellar angiogenesis in parallel with neurogenesis, potentially contributing to the neurodevelopmental deficits observed in AOP. Thus, the interconnected nature of angio- and neurogenesis during cerebellar development makes it crucial to take vascular aspects into account in therapeutic approaches to neurodevelopmental disorders.

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Standardising research on marine biological carbon pathways required to estimate sequestration at Polar and sub-Polar latitudes - Simon A. Morley; David K.A. Barnes; Camila Neder; Ricardo Sahade; Chester J. Sands; Carla M. de Aranzamendi; Kaja Balazy; Piotr Balazy; Facundo Barrera; Narissa Bax; Sofia Becerra; Lucia Bergagna; et al. (Earth-Science Reviews, 2026)

Hydraulic Fracture Propagation in Pre-structured Media: Stress Field and Fracture Network Topology - Adrian V. Garcia; Rached M. Rached; Carlos D. Rodriguez-Hernandez; J. Carlos Santamarina (Rock Mechanics and Rock Engineering, 2026)

Contributions to the knowledge of DNA barcodes and diversity of intertidal and shallow-water mollusks in the Beagle Channel - L. D. Chiberry; J. Sánchez; V. M. Núñez; S. Rodriguez; M. Pellegrino; S. Poljak (Polar Biology, 2026)

Evidence of deep-sea trophic resource partitioning between the glowbellies Acropoma hanedai and A. japonicum near Southwestern Taiwan - Michael J. Ghedotti; Kurt L. Riggin; Milo A. Marsh; Sarah A. Bramlett; Hayden D. Pearson; Gabriel J. Rodriguez; Josephine N. Gruber; Joshua P. Egan; Kristofor A. Voss (Environmental Biology of Fishes, 2026)

‘Building the (Im)perfect Beast’: Strategies for Identifying Appropriate Spatial Stock Assessment Model Complexity From an International, Blinded High‐Resolution Simulation Experiment - Aaron M. Berger; Daniel R. Goethel; Simon D. Hoyle; Patrick Lynch; Caren Barceló; Alistar Dunn; Brian J. Langseth; Carolina Minte‐Vera; Jemery Day; Haikun Xu; Francisco Izquierdo; Dan Fu; et al. (Fish and Fisheries, 2026)
Despite their potential to inform sustainable regional harvest and climate‐resilient fisheries management, spatial stock assessment models remain underused for management advice. To identify barriers that inhibit broader use of these methods, we conducted a blinded international simulation experiment mimicking real‐world stock assessment development when confronting spatial complexity. Seven analyst teams built spatially aggregated and spatially explicit assessment models using data simulated from high‐resolution operating models based on Indian Ocean yellowfin tuna and Ross Sea Antarctic toothfish dynamics. Each team documented how assessment software platform, data analyses, model building approach, and diagnostics influenced model complexity and realism. A consensus emerged on key assessment building approaches: (1) conduct high‐resolution data analyses to identify appropriate spatial structure; (2) start with simplified models and incrementally add complexity; (3) iteratively evaluate diagnostics to determine necessary spatial complexity; and (4) maintain models with different spatial structures to aid interpretation. The experiment also revealed several valuable insights for parameterising assessments, including consideration of data pre‐processing with spatiotemporal models to better inform data‐sparse regions; regression trees to identify fleet and spatial structure; trade‐offs in complexity between productivity and movement dynamics to achieve tractable and stable model structures; and ensemble modelling approaches to address structural uncertainty. Our findings demonstrate that international collaborations and simulation experiments are crucial for addressing challenges in implementing spatial stock assessments and for evaluating whether their added complexity is justified given management objectives. Broader collaborations are encouraged to foster innovation in fisheries management and to help recognise the practical trade‐offs between model parsimony and complexity.

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Aquaculture shapes antibiotic resistance in Mediterranean gilthead sea bream farming: From hatcheries to offshore cages - Marco Basili; Eleni Nikouli; Frederik D. Møller; Konstantinos A. Kormas; Gian Marco Luna; Veronica Tolosa-Enguís; Sonia M. Rodriguez-Ruano; Yolanda Sanz; Marco Candela; Grazia Marina Quero; Frank M. Aarestrup; Pimlapas Leekitcharoenphon (Aquaculture, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Continental Contrasts in Climate Extremes That Control Tree Fecundity - James S. Clark; Robert Andrus; Margarita Arianoutsou; Davide Ascoli; Yves Bergeron; Michal Bogdziewicz; Thomas Boivin; Raul Bonal; Thomas Caignard; Maxime Cailleret; Rafael Calama; J. Julio Camarero; et al. (Global Change Biology, 2026)
In 2023, more than half of olive harvests ( Olea europaea ) across Spain, Greece, and Türkiye were lost to drought. The same year late freeze destroyed 90% of the peach crop ( Prunus persica ) on the Georgia Piedmont and the apple crop ( Malus domestica ) in central New York, Vermont, and southern Quebec. Climate extremes now rank with the costliest threats to agriculture, but their role in forest recovery from diebacks that are happening globally is unknown for lack of tree fecundity estimates in forests. Tolerance of climate extremes could depend on past exposure but constrained by phylogenetic conservatism. We report a continental scale analysis of climate extremes and forest fecundity across North America and Europe showing that responses to late freeze and drought are happening now. Species differences are not explained by the traits typically included in ecological studies and they are weakly associated with phylogeny. Late freeze, that is, freezing temperatures that follow the onset of flower development in spring, is shown to be “normal” in North America, but not Europe, potentially explaining failed seed production due to delayed onset and the resultant shorter growing period by North American transplants dating back at least to the 18th century. Drought has thus far had the greatest impacts in dry forested regions, but here too, species differences are not explained by traditional trait values. If responses have been buffered from drought and late freeze by past exposure, acclimation and local adaptation prove inadequate as extremes intensify.

Impacts of Diverse Stakeholder Participation on Fisheries Management - Sangeeta Mangubhai; S. L. Smith; Z. Davis; N. Koedyker; J. Augustyn; D. Durholtz; S. Fulton; Harlisa; M. T. Hidayat; L. Hiriart-Bertrand; M. Khazali; E. Litsinger; et al. (Coastal Management, 2026)

Identifying and quantifying greenhouse gas emissions with the AVIRIS-3 airborne imaging spectrometer - Red Willow Coleman; Andrew K. Thorpe; Philip G. Brodrick; Adam Chlus; Jay E. Fahlen; Brian Bue; John Chapman; Regina F. Eckert; Daniel J. Jensen; Michael L. Eastwood; David R. Thompson; Clayton D. Elder; et al. (Remote Sensing of Environment, 2026)

Physicochemical Differences Observed in Photostability Studies of Lyophilized, Reconstituted, and Diluted Somatropin - Jordan D. Pritts; Uriel Ortega-Rodriguez; V. Ashutosh Rao (Pharmaceutical Research, 2026)
Background While photostability testing conditions for biologics are often based on small molecule standards, the unique characteristics of proteins necessitate a deeper understanding of appropriate testing and controls. This study examines the effects of light stress on various presentations of somatropin, a therapeutic growth hormone. Methods Somatropin was exposed to light in lyophilized, reconstituted, and diluted forms. Quality attribute changes were analyzed using size exclusion chromatography, micro-fluidic imaging, imaged capillary isoelectric focusing, and liquid chromatography mass spectrometry (LC–MS). Results Light stress increased high molecular weight species (HMWS), particularly in liquid formulations, as shown by size exclusion chromatography (Lyophilized + 0.4%, Reconstituted + 2.7%, Diluted + 4.7%). Micro-fluidic imaging revealed no change in particle formation. All presentations exhibited shifts in charge variants, with increases in acidic species (Lyophilized + 2.8%, Reconstituted + 7.8%, Diluted + 6.2%) and basic (Lyophilized + 0.4%, Reconstituted + 0.7%, Diluted + 0.8%) . Liquid chromatography-tandem mass spectrometry (LC–MS/MS) peptide mapping detected increased methionine oxidation in light-exposed samples, correlating with higher protein concentration (M14- Lyophilized + 2.3%, Reconstituted + 7.4%, Diluted + 2.7%, M125- Lyophilized + 2.5%, Reconstituted + 2.9%). Diluted somatropin showed higher HMWS levels but reduced methionine-125 oxidation susceptibility compared to reconstituted formulations. Conclusions Light exposure altered product quality attributes, with more pronounced effects on liquid presentations. These findings provide insights into the distinct impacts of light exposure on different drug presentations throughout their lifecycle, highlighting the importance of tailored photostability testing for different product presentations of biologic drugs.

Integrative systematics of the Brazilian tree “sucupira”: morphological, cytogenetic and genomic boundaries of Pterodon emarginatus Vogel and P. pubescens (Benth.) Benth. (Leguminosae, Papilionoideae) - Victória B. Albernaz; Yennifer Mata-Sucre; Mariela A. Sader; Pablo E. Rodriguez; Cíntia P. Targueta; Adriana M. Antunes; Rafael B. Pinto; André Marques; Dulce Maria Sucena D. A. Rocha; Gustavo Souza; Thannya N. Soares (Systematics and Biodiversity, 2025)

The Guajira contourite depositional system along the northern Colombian Caribbean convergent margin - J. Naranjo-Vesga; O. Mantilla; D. Rincón-Martínez; E. Rodriguez-Rubio; A. Ortiz-Karpf; C. Winter; Y. Rojas-Agramonte (Marine and Petroleum Geology, 2025)

Environmental identities of college students reveal potential conflicts and common ground for wildlife conservation - Richard Von Furstenberg; Lincoln R. Larson; M. Nils Peterson; Kangjae Jerry Lee; Victoria R. Vayer; kathryn stevenson; Stacy A.C. Nelson; Jeremy Bruskotter; Adam A. Ahlers; Christine Anhalt-Depies; Taniya Bethke; Chris Chizinski; et al. (Biological Conservation, 2025)

Effect of Probiotics on Sperm Quality in the Adult Mouse - Ana Sanchez-Rodriguez; Ingrid I. D. Idrovo; Rocío Villafranca; Nerea Latorre; Juan Antonio Rielo; Ane Laburu; Sandra Nieto-Román; Daniel Heredia; Rubén González; Virginia García-Cañas; Diego Laxalde; Carolina Simó; et al. (Probiotics and Antimicrobial Proteins, 2025)
The administration of probiotics for the treatment of different diseases has gained interest in recent years. However, few studies have evaluated their effects on reproductive traits. The objective of this study was to examine the effect of two mixtures of probiotics, a commercial probiotic (Vivomixx®) and a mix of Lacticaseibacillus rhamnosus GG and Faecalibacterium duncaniae A2-165, on sperm quality in a mouse model. Adult male mice (8 months old) were used for two experimental and one control groups ( n = 5 each). The probiotics or physiological serum (control) was administered orally, twice a week, during 5 weeks. Sperm were collected from the cauda epididymis, and their total number, motility, kinematics, morphology, and acrosome integrity were assessed in recently collected samples and after a 60-min in vitro incubation. Results showed a higher percentage of normal sperm in both experimental groups, with fewer head abnormalities than in the control. Differences were found among groups in the morphometry of sperm heads, being more elongated in mice treated with probiotics. Sperm from probiotic-treated mice showed similar total motility when compared to the controls, although the proportion of progressively moving sperm and their vigor of motility were lower. Sperm swimming descriptors were measured with a CASA system. Velocity parameters were similar among groups whereas linearity was higher in mice treated with the commercial probiotic. These results suggest that the administration of probiotics may increase the proportion of sperm with normal morphology and lead to modifications in sperm head shape that may enhance sperm swimming. Studies using a longer administration period would be useful in further characterizing the effect of these probiotic mixtures on sperm quality and fertilization capacity.

A Simple Model to Estimate the Economic Optimum Nitrogen Rate in Potato Using Vegetation Indices - Claudia M. Giletto; W. D. Carciochi; F. M. Inchauspe; S. E. Silva; M. N. Cassino; V. Ortega; S. Rodriguez; J. C. Laborde Amador; N. Reussi Calvo (Potato Research, 2025)

Assessment of microplastic retention efficiency using pilot-scale filtration systems applied to drinking water - K. Herrera; A. Egea-Corbacho; D. Coello; J. Quiroga; E. Marin; V. Monsalvo; E. Lucero; R. Rodriguez (Journal of Hazardous Materials, 2025)

A comprehensive analysis of the nitrogen synchrony between cover crops release and maize uptake - Walter D. Carciochi; Francisco Cafaro La Menza; Denis G. Terwissen Gjerloff; Nahuel I. Reussi Calvo; Guillermo A. Divito; Oscar R. Avila Manotoa; María P. Rodriguez; Sergio Tovar Hernández; Adrian M. Lapaz Olveira; Hernán R. Sainz Rozas; Pablo A. Barbieri (Plant and Soil, 2025)

Telomere Length Differences Indicate Climate Change‐Induced Stress and Population Decline in a Migratory Bird - Marina D. Rodriguez; Rachael A. Bay; Kristen C. Ruegg (Molecular Ecology, 2025)
Genomic projections of (mal)adaptation under future climate change, known as genomic offset, faces limited application due to challenges in validating model predictions. Individuals inhabiting regions with high genomic offset are expected to experience increased levels of physiological stress as a result of climate change, but documenting such stress can be challenging in systems where experimental manipulations are not possible. One increasingly common method for documenting physiological costs associated with stress in individuals is to measure the relative length of telomeres—the repetitive regions on the caps of chromosomes that are known to shorten at faster rates in more adverse conditions. Here we combine models of genomic offsets with measures of telomere shortening in a migratory bird, the yellow warbler ( Setophaga petechia ), and find a strong correlation between genomic offset, telomere length and population decline. While further research is needed to fully understand these links, our results support the idea that birds in regions where climate change is happening faster are experiencing more stress and that such negative effects may help explain the observed population declines.

The key mechanisms associated with the survival of Gulf toadfish, Opsanus beta , when in severe hypoxia - Anastasiya Plotnikova; Isabelle R. Nelson; Shara Y. Sookhoo; Jacob M. Belkin; Vanessa P. Lima; Ross D. Bronfman Bunch; Athena M. Santomero; Sophia A. Santomero; Emily C. Rodriguez; Jayda K. Rodriguez; Kathleen M. Davis; Amanda J. Kaplan; et al. (Journal of Fish Biology, 2025)
Florida's shallow seagrass beds experience daily diurnal fluctuations in environmental oxygen, leading to hypoxic episodes (PO 2 −1 , ~6 kPa) that have increased in frequency and intensity in recent decades. The native Gulf toadfish ( Opsanus beta ) have been shown to employ a suite of adaptive cardiovascular, ventilatory and metabolic adjustments to survive moderate hypoxia, but little is known of the mechanisms used to survive severe hypoxia. The objective of this study was to characterize the acute response of Gulf toadfish to severe hypoxia ( 2 ~0.4 kPa for 3 h followed by 1 h recovery). Heart rate, pulse pressure, caudal arterial blood pressure, ventilation frequency and ventilation amplitude were monitored and blood samples were taken from both groups and analysed for pH, glucose, lactate and other endpoints. Hypoxia‐exposed fish experienced a statistically significant 70% decrease in heart rate and a 32% decrease in ventilation frequency during hypoxia exposure. Moreover, plasma glucose concentrations increased 5‐fold and plasma lactate concentrations increased 6‐fold, with a minimal reduction in pH. Our findings support our hypothesis that Gulf toadfish are highly hypoxia tolerant and survive severe hypoxia by reducing energy expenditure and switching to anaerobic metabolism. It is important to understand how the Gulf toadfish deal with severe hypoxia due to the increasing prevalence of severe hypoxia in its natural environment.

Ecological Risk–Benefit Analysis for Assisted Colonization - Rafael D'Andrea; György Barabás; Sarah E. Dalrymple; Wendy Foden; Piero Genovesi; Meghna Krishnadas; Mathew A. Leibold; Mark A. McPeek; Axel Moehrenschlager; Jon Paul Rodriguez; H. Reşit Akçakaya (Global Change Biology, 2025)
Assisted colonization (AC), translocating a species outside its indigenous range to avoid its extinction, is one of the few conservation options for some species. It is also controversial because of the history of ecological impacts of invasive species, including the extinction of native species as a result of novel ecological interactions resulting from the introduction. Although several national and international organizations have issued guidelines related to AC, none allow case‐specific decision‐making based on risks and benefits to biodiversity. We propose a two‐pronged approach to fill this gap. The first step aims to separate clear‐cut cases of AC from those that require an in‐depth risk analysis. We propose a set of seven qualitative criteria to identify AC projects that are clearly low‐risk and high‐benefit, and therefore should not be controversial, and those that are clearly high‐risk or low‐benefit and therefore should not be attempted. This identifies only the most obvious cases, leaving out many cases to be determined through a quantitative analysis to estimate the probabilities of extirpation of the resident species because of AC, which is the second step of our approach. We propose a roadmap for developing such a system based on community ecology theory, and a framework for considering the estimated probabilities in a global context. Our framework recommends an AC project only if it would result in a larger number of globally extant species than a scenario of no action. We propose large‐scale testing of the clear‐cut approach, further development of the quantitative approach, and wide consultation for adopting international guidelines for risk assessment of AC projects.

Association of Immunogenicity and Drug Exposure and the Importance of Target Engagement in ADA Development: A Clinical Case Study of Anti-SARS-CoV-2 Biotherapeutics - Susan C. Irvin; Samit Ganguly; Zhiqiang Wang; Zhongqing Will He; Marguerite Alejandro; Kaitlin Donohue; Chinnasamy Elango; Chris Gallo; Stephen Guttmann; Shawn Kalicharan; Kristina Kameron; James Laird; et al. (The AAPS Journal, 2025)
The administration of therapeutic proteins, such as monoclonal antibodies (mAbs) may result in the formation of anti-drug antibodies (ADA), but there is limited publicly available data for biotherapeutics with exogenous targets or with targets in low abundance systemically. ADAs can impact a biotherapeutic’s safety, efficacy, and pharmacokinetics, so evaluation of immunogenicity is required for all therapeutic proteins. This analysis sought to evaluate the immunogenicity of two mAbs against COVID-19, casirivimab (CAS) and imdevimab (IMD) administered as a cocktail (CAS + IMD), in multiple clinical trials across different participant populations to add knowledge about the immunogenicity risk of protein therapeutics against exogenous targets and the association between immunogenicity and drug exposure. Overall, the incidence of treatment-boosted and treatment-emergent ADAs and neutralizing antibodies in both disease treatment and prophylaxis settings were low (i.e., < 11%). Participants in these studies were followed for up to 225 days post-last dose. Over time, the incidence of treatment-emergent and treatment-boosted immunogenicity for each mAb increased, but the rates and titers remained low overall; when it developed, patients usually developed ADA to both mAbs. Frequency of administration, dose, and route of administration did not appear to impact rates of immunogenicity. Concentrations of CAS and IMD were similar between participants of different immunogenicity status, indicating immunogenicity of CAS and IMD had no impact on pharmacokinetics of these mAbs; there was also no observed impact on safety or efficacy. The data presented here may provide supportive information for assessing the immunogenicity risk of protein therapeutics with exogenous targets. Graphical Abstract

Improving the Volume-based Feeding Process in Intensive Care Units - K. Bolender; D. Rodriguez-Brindicci; K. Hung (Journal of the Academy of Nutrition and Dietetics, 2025)

Preventing Tube Feeding Errors with the Use of Barcode Medication Administration (BCMA) Technology - D. Rodriguez-Brindicci (Journal of the Academy of Nutrition and Dietetics, 2025)

Fungal communities in biowaste composting: a comparative study of multiple ratios of woodchips vs. a perlite-cardboard blend as bulking agents - Leonardo Guidoni; Émilie D. Tremblay; Hervé Van der Heyden; Carmen Morales-Rodriguez; Andrea Vannini (Journal of Environmental Management, 2025)

Multi-wavelength internal standardization using inductively coupled plasma optical emission spectrometry - Reagan Elia; Thomas J. Johnston; Alberto D. Figueroa; Emily M. Curbow; Mayra S. Gonzalez Guzman; Leah C. Rodriguez Cabrera; Marisa M. Morcom; Willis B. Jones (Analytica Chimica Acta, 2025)

Nutritional Ecology of Lactation in Franciscana Dolphins ( Pontoporia blainvillei ) From Argentina - Pablo Denuncio; M. Candela Macagno; Antonella D. Padula; M. Agustina Mandiola; Juan P. Loureiro; María Julieta Olocco Diz; M. Fernanda Zapata; Diego Rodriguez; Gabriel E. Machovsky‐Capuska (Marine Mammal Science, 2025)
Milk production strategies, duration, and composition vary among mammals. Odontocete cetaceans exhibit a long lactation strategy characterized by high parental investment and prolonged nutritional dependence. Understanding the nutritional demands of these offspring during lactation is complex, particularly due to their aquatic lifestyle. This study examines the nutritional dynamics of endangered Franciscana dolphins ( Pontoporia blainvillei ) during their first year of life. Our findings indicate that Franciscana milk is energy‐rich, with proteins and lipids as primary energy sources, varying in proportion throughout lactation. Summer milk has a higher protein‐to‐lipid ratio and lower energy density, while winter milk is more energy‐dense, with a greater lipid proportion and increased variability in composition. Calves over 80 cm consume a combination of low protein‐to‐lipid ratio milk with high protein‐to‐lipid ratio prey. Artificial milk formulas used in rehabilitation closely resemble the macronutrient composition of wild milk. This study provides valuable insights into the critical life stage of this vulnerable species and contributes to developing nutritional protocols for rehabilitating live‐stranded individuals.

Improving the Nutrition Focused Physical Exam Process to Identify and Address Malnutrition in Acute Care - K. Hung; D. Rodriguez-Brindicci (Journal of the Academy of Nutrition and Dietetics, 2025)

Assessment of the polyphenol recovery from white wine lees via non-ionic polymeric resins - Martina Gaglianò; Antonio D. Rodriguez-Lopez; Carmela Conidi; Alfredo Cassano; Giuseppina De Luca; Esperanza M. Garcia-Castello (Journal of Food Engineering, 2025)

Soil functions are shaped by aridity through soil properties and the microbial community structure - Anna Doménech-Pascual; Luciana Chavez Rodriguez; Xingguo Han; Joan Pere Casas-Ruiz; Joan Ferriol-Ciurana; Jonathan Donhauser; Karen Jordaan; Steven D. Allison; Aline Frossard; Anders Priemé; Jean-Baptiste Ramond; Anna M. Romaní (Applied Soil Ecology, 2025)

Network of networks: Time series clustering of AmeriFlux sites - David E Reed; Housen Chu; Brad G. Peter; Jiquan Chen; Michael Abraha; Brian Amiro; Ray G. Anderson; M. Altaf Arain; Paulo Arruda; Greg A. Barron-Gafford; Carl Bernacchi; Daniel P. Beverly; et al. (Agricultural and Forest Meteorology, 2025)

Seasonal variation of trifluoroacetic acid (TFA) in Antarctic ice cores analysed by direct injection non-suppressed ion chromatography-mass spectrometry (nsIC-MS) - Estrella Sanz Rodriguez; Mingxia Lai; Harrison Stevens; Meredith K. Nation; Christopher T. Plummer; Lenneke M. Jong; Jason L. Roberts; Andrew D. Moy; Andrew R. Bowie; Mark A. Curran; Brett Paull (Science of The Total Environment, 2025)

Biochar-enhanced bioreactors for agricultural nitrogen mitigation - Jason P. Andras; Rachel L. Rubin; William G. Rodriguez-Reillo; Casey D. Chatelain; Oleander Morrill; Kate A. Ballantine (Journal of Environmental Management, 2025)

Biophysical and biochemical limitations to photosynthesis and yield of peanut (Arachis hypogaea L.) under water-deficit stress - Bishwoyog Bhattarai; Harsimran Kaur-Kapoor; Alexander Rodriguez; Mark D. Burow; Glen L. Ritchie; Lindsey C. Slaughter; Jasmine Neupane; Haydee E. Laza (Plant and Soil, 2025)
Aims Global peanut production is constrained by the frequency and severity of drought. New insights into photosynthetic biophysical and biochemical limitations under water-deficit stress are important to enhance peanut photosynthetic efficiency and production. This study examines the combined effects of water deficit, genotype, and growth stage on peanut physiology. Methods An experiment was conducted during three growing seasons (2020 – 2022) to evaluate peanut genotypes (AG18, C76-16, GA-09B, and Lariat) at three developmental stages: flowering/peg development ( R 2 -stage ), pod initiation/seed development ( R 4 -stage ), and pod filling/initiation of crop maturity ( R 7 - stage ). The study was carried out under well-watered and water-deficit conditions. We quantified the biophysical (stomatal conductance) and biochemical limitations [the maximum rate of carboxylation ( V c, max ), rate of RuBP regeneration ( J max ), and photosynthetic electron transport rate ( ETR )]. Results The drought-induced reduction in A N during the R 2 -stage stage was primarily attributed to a significant decrease in stomatal conductance ( g s ). In contrast, at the R 7 -stage , the reduction in A N was driven by limitations in the g s , V c, max , and J max . Notably, at the R 7 -stage , genotypes C76-16 and Lariat showed higher g s , ETR , and V c, max , contributing to increased A N and enhanced pod and kernel yield compared to AG18 and GA-09B. Conclusion A N reduction was driven by the biophysical limitation at the R 2 -stage and a combination of biophysical and biochemical limitations at the R 7 -stage. Furthermore, physiological strategies such as maintaining higher stomatal conductance while reducing photosystem II damage, as shown by C76-16, could be an effective drought tolerance strategy for maintaining high pod yield.

Active and passive pathways of nutrient transfer in coral reef ecosystems - Ruth E. Dunn; Nicholas A. J. Graham; Laura-Li Jeannot; Rucha Karkarey; F. Javier Gonzalez-Barrios; Ines D. Lange; Julia Rodriguez Fillol; Ronan Roche; Marleen Stuhr; Cassandra E. Benkwitt (Coral Reefs, 2025)
Coral reefs receive both passive and active nutrient subsidies, supplied via oceanographic processes and animal-mediated transfer, which can bolster reef productivity and resilience to disturbance. We examined the relative importance of these two pathways across lagoonal and seaward reefs, reefs of different depths, and those around islands either with or without breeding seabird colonies using carbon and nitrogen stable isotopes (ð 13 C and ð 15 N) and nutrient metrics (per cent N, %N and carbon-to-nitrogen ratios, C:N). We found increased passive oceanic nutrient inputs in reefs that were both deep and seaward facing, indicated by lower ð 13 C values. Enriched ð 15 N values and lower carbon-to-nitrogen ratios within reefs adjacent to islands with seabird colonies provided evidence of the role of seabirds as active vectors of nutrients to coral reef food webs, particularly within shallow, lagoonal reefs. Though %N values did not seem to provide a good indicator through which to disentangle active vs passive nutrient transport within this context, variation in ð 13 C and ð 15 N values and C:N ratios highlighted the interplay between passive oceanic processes and active seabird contributions to coral reefs. We emphasise the importance of both preserving and restoring natural nutrient pathways, particularly at a time when coral reef ecosystems are under increasing pressure from anthropogenic threats.

Iron and nitrate availability modulate trace metal quotas and macromolecule production of Tetraselmis tetrahele - Dolly C. Manic; Richard D. Redil; Irene B. Rodriguez (Algal Research, 2025)

The Impact of Disturbance on Tree Size Distributions in the United States - Adam J. Eichenwald; John M. Grady; Jonathan A. Knott; Quentin D. Read; J. Marcos Rodriguez; Sydne Record (Global Ecology and Biogeography, 2025)
Aim Tree size distributions are an emergent feature of forest dynamics across space and time. Theory suggests that undisturbed forests exhibit a size‐abundance distribution captured by a power‐law relationship with a near‐2 slope. We aimed to quantify how disturbances systematically and predictably cause deviations from this expected pattern. Location Contiguous United States. Time Period 2001–2023. Major Taxa Studied Diverse tree communities. Methods We analysed size‐abundance distributions in over 160,000 FIA plots for both disturbed and undisturbed forests, examining changes in slope associated with disturbances, stand age, and maximum tree height. We used a Structural Equation Model (SEM) to evaluate whether disturbance effects on size‐abundance slopes were indirectly mediated by changes in stand age or maximum height. Results We found that the predominant disturbances across the dataset (e.g., ground fires, animal damage) result in predictable flattening of size‐abundance slopes, reflecting the selective removal of smaller trees. In contrast, many disturbances (e.g., wind, disease) did not shift the slopes predictably, indicating that they did not selectively impact any specific size class. Maximum tree height and stand age were also reliable predictors of size‐abundance distributions, but a structural equation model demonstrated that the impact of disturbance on size‐abundance slopes was not mediated through its indirect effects on stand age or maximum tree height, suggesting a direct pathway of influence. Main Conclusions Disturbances result in predictable changes to forest size‐abundance slopes. As climate change and increased disturbance frequencies produce younger and shorter forests, future size‐abundance slopes are expected to be steeper than those in undisturbed forests. Our findings suggest a temporary flattening in the size‐abundance relationship immediately after the predominant disturbances across the dataset (ground fires, animal damage). These findings underscore the importance of understanding disturbance impacts on forest size structure to improve predictions of forests across broad spatial and temporal scales.

Evaluating 3D-Printed Pre-separator Inserts in a Fast Screening Impactor for Physicochemical Characterization of Fine Particle Dose Release from Dry Powder Inhalers - Nathan A. Reed; Roee Dar; Nicholas Holtgrewe; Leo N. Y. Cao; Xiaofei Liu; Denise S. Conti; Bryan Newman; Elizabeth Bielski; Jason D. Rodriguez; Changning Guo (AAPS PharmSciTech, 2025)

Enzymatic hydrolysis altered the physicochemical and immunogenic profile of protein-based ingredients derived from industrial hempseed (Cannabis sativa L.) - Abby Rodriguez; Bingqi Chen; Philipus Pangloli; Doris D'Souza; Hari B. Krishnan; Vermont P. Dia (Food Bioscience, 2025)

Wavelet analysis and sinusoidal modelling of environmental variables in a weaned piglet farm - Maria D. Fernandez; Manuel R. Rodriguez; Xose R. Fdez-Vidal; Roberto Besteiro (Building and Environment, 2025)

Urban Tree Growth and Drought Responses Show Evidence of Climate Resilience - Manuel Esperon‐Rodriguez; Matthew Brookhouse; Sally A. Power; Diego Avi; Thomas Baer; Paul D. Rymer; Mark G. Tjoelker (Global Change Biology, 2025)
Climate change has a negative impact on the vitality of forests, and drought and heatwaves are the most influential abiotic stressors that contribute to tree health decline and mortality. Urban trees are not only vulnerable to climate change, but they also face harsh environmental conditions, including the urban heat island effect, limited soil volume and water availability. Therefore, the long‐term sustainability of urban forests relies on healthy and thriving trees and the identification of species that are resilient to climate change. Thus, it is fundamental to understand how urban trees respond to environmental conditions, including climate. This study investigates how urban trees respond to both long‐term climatic conditions and episodic extreme climate events. We evaluated variation in urban tree growth across differing climates by reconstructing growth histories and developing drought response indices. We selected 10 tree species planted in seven cities distributed along temperature and precipitation gradients across the Australian continent. We determined spatial and temporal patterns of tree‐ring growth in relation to extreme climate events. We found significant differences among cities, suggesting that local environmental conditions significantly influence tree growth. While some species showed fast annual growth in cool and wet cities, other species had similar growth across all cities or even faster growth in hot and dry cities. Urban trees generally responded positively to wetter conditions during the warmest month, which might be related to longer growing seasons and water availability. We found a positive effect of extreme hot conditions on growth, suggesting that urban trees might be well adapted to warm urban environments. Species climate‐growth relationships can help guide species selection to maximize benefits delivered by urban forests and minimize environmental and socio‐economic losses under current and future climates.

Dynamic effect of climate change on flood damage cost in the Andean region of Colombia using an ARDL-ECM model and climate change projections - Camilo A. Rodriguez-Espinosa; Carlos F. Valencia; Carlos G. Ramirez; Carlos D. Valencia (Sustainable Cities and Society, 2025)

Extreme marine heatwave linked to mass fish kill in the Red Sea - Matthew D. Tietbohl; Lily G.C. Genevier; Erik C. Krieger; Alexander Kattan; Yixin Wang; Elamurugu Alias Gokul; Lucia M. Rodriguez Bravo; Lea Palm; Gage Mele; Ibrahim Hoteit; Maggie D. Johnson (Science of The Total Environment, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

The importance of tropical tree-ring chronologies for global change research - Peter Groenendijk; Flurin Babst; Valerie Trouet; Ze-Xin Fan; Daniela Granato-Souza; Giuliano Maselli Locosselli; Mulugeta Mokria; Shankar Panthi; Nathsuda Pumijumnong; Abrham Abiyu; Rodolfo Acuña-Soto; Eduardo Adenesky-Filho; et al. (Quaternary Science Reviews, 2025)

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Durum wheat kernel contamination by mycotoxigenic fungi and mycotoxins as affected by soil tillage and fertilization management in a Mediterranean environment - Merima Jasarevic; Carmen Morales Rodriguez; Giuseppina Scialò; Barbara De Santis; Francesca Debegnach; Arianna Palchetti; Luca D’Ambrosio; Elisabetta Caprai; Gaetan Minkoumba Sonfack; Roberto Mancinelli; Alessia Catalani; Gabriele Chilosi (Journal of Plant Pathology, 2025)

Enhanced built-in electric fields in alkali metal-doped C3N5 enable sustainable molecular oxygen activation for water purification - Bin Yang; Liliang Lu; Qian Zhang; Guixiang Ding; Guangfu Liao; Mei Zhang; Xinghuan Liu; Raul D. Rodriguez; Xin Jia (Chemical Engineering Journal, 2025)

Social and knowledge diversity in forest education: Vital for the world’s forests - Mika Rekola; Andrew B. Taber; Terry L. Sharik; John A. Parrotta; Michael J. Dockry; Folaranmi D. Babalola; Tara L. Bal; David Ganz; Marta Gruca; Manuel R. Guariguata; James Kungu; Pipiet Larasatie; et al. (Ambio, 2025)
A global assessment of the status of tertiary, vocational, and technical forest education and training found deficits in inclusion of knowledge and student diversity. Coverage of forest services and cultural and social issues was characterized as weak in the curricula of many programs. The inclusion of traditional and Indigenous knowledge was frequently poor or absent. Gaps were found in enrollment at tertiary education levels with respect to diversity by gender, race/ethnicity, and other societal groups. If unaddressed, forest researchers, professionals, and workers will continue to lack familiarity with different knowledge systems and the importance of inclusive representation. Improvements in forest education related curricula, research, monitoring, policy, recruitment, and promotion are recommended. Without remedial action to build a representative, skilled, and knowledgeable workforce, prospects for forests to meet local, national, and global goals are at risk. Improved social and knowledge diversity in forest education is paramount for the future of forests.

A nation-wide urban trial network of tree and shrub climate resilience - Manuel Esperon-Rodriguez; Sally A. Power; Mark G. Tjoelker; Mahmuda Sharmin; Paul D. Rymer (Urban Forestry & Urban Greening, 2025)

A global soil spectral grid based on space sensing - José A.M. Demattê; Rodnei Rizzo; Nícolas Augusto Rosin; Raul Roberto Poppiel; Jean Jesus Macedo Novais; Merilyn Taynara Accorsi Amorim; Heidy Soledad Rodriguez-Albarracín; Jorge Tadeu Fim Rosas; Bruno dos Anjos Bartsch; Letícia Guadagnin Vogel; Budiman Minasny; Sabine Grunwald; et al. (Science of The Total Environment, 2025)

Developmental exposure to an environmentally relevant dose of Bisphenol S impairs postnatal growth and disrupts placental transcriptional profile in female rat - J. Fudvoye; D. Lopez-Rodriguez; C. Glachet; D. Franssen; Q. Terwagne; A. Lavergne; A.F. Donneau; C. Munaut; P. Dehan; A. Lomniczi; A.S. Parent (Reproductive Toxicology, 2025)

Thermal analysis of multi-layered glazed window under Mexican climate - I. Zavala-Guillén; D. Barrera-Román; F. Noh-Pat; Miguel Sidón; D. García-Pérez; A. Rodriguez-Ake (Energy and Buildings, 2025)

The use of lichens and mosses as sentinel organisms for the determination of the airborne organic pollution in Western Pyrenees: The case of the Irati forest - J. Bustamante; A. Gredilla; O. Liñero; D. Amouroux; D. Elustondo; J.M. Santamaría; A. Rodriguez-Iruretagoiena; S. Fdez-Ortiz de Vallejuelo; G. Arana; A. de Diego (Atmospheric Pollution Research, 2025)

Gluconacetobacter diazotrophicus triggers ISR involving SA and JA/Et defense-related pathways to respond against Ralstonia solanacearum in Arabidopsis and optimizes the cellular redox state maintaining reduced FITNESS levels - María Sol Srebot; María Belén Ripa; Julieta Andrea Gallozo; Gabriel Roberto Bettucci; Matías Damián Ferretti; Luciano David D´Attilio; María Laura Martínez; Elena Graciela Orellano; María Victoria Rodriguez (Plant and Soil, 2025)

Bridges monitoring and assessment using an integrated bim methodology - D. Rodriguez Polania; F. Tondolo; A. Osello; M. Piras; V. Di Pietra; N. Grasso (Innovative Infrastructure Solutions, 2025)
Risk assessment of long-existing infrastructure has become one of the main challenges in civil engineering. Major efforts have been made in recent years to develop new techniques for rapid damage identification and ensure proper management of these structures. This paper presents a data management approach utilizing BIM methodology to create a digital database for bridge monitoring procedures. Initially, two BIM methodologies for creating a damage database are introduced, focusing on beams from a dismantled urban viaduct. Subsequently, the most suitable methodology is applied to an existing bridge in Turin, Italy. Through the chosen methodology a damage identification and classification process based on a triangular mesh is performed, assisted by a convolutional neural network (CNN) for automatic damage detection. Additionally, the paper outlines a digitalization process within a BIM environment, integrating official guidelines for bridge risk evaluation, classification, and monitoring in Italy. By employing programming tools, all data required by the guidelines is efficiently incorporated into the database. The outcomes demonstrate the effectiveness of remote sensing applications for bridge inspection and the possibility of merging BIM methodology into the inspection process to enhance the damage assessment of existing structures.

Promoting Workplace Health, Safety, and Well-Being Among Essential Agricultural Workers Through Vaccine-Preventable Infectious Diseases Training in the Rio Grande Valley - Anabel Rodriguez; David I Douphrate; Ana L Pineda Reyes; Susana Zavala; Andrea V. Cabrera Cruz; Maria D Alegria; Brian Ukaegbu; Annie J Keeney; Brenda Berumen-Flucker; Eva M Shipp; Shannon P Guillot-Wright; Maria E Fernandez-Esquer; et al. (Journal of Agromedicine, 2025)

Microplastics in the digestive tract of an endangered cetacean of the Southwest Atlantic Ocean: The franciscana dolphin - Antonella D. Padula; Ana C. Ronda; Lucas S. Rodríguez Pirani; A. Lorena Picone; Rosana M. Romano; Gisela V. Giardino; Juan Pablo Seco Pon; Rodrigo Machado; Marcela Gerpe; Diego Rodriguez; Pablo Denuncio (Marine Pollution Bulletin, 2025)

The diurnal variation of dust and water ice aerosol optical depth at Jezero crater observed by MEDA/TIRS over a full Martian year - Michael D. Smith; Germán M. Martínez; Eduardo Sebastián; Mark T. Lemmon; Samuel A. Atwood; Daniel Toledo; Daniel Viúdez-Moreiras; Aurélien Stcherbinine; Jose Antonio Rodriguez-Manfredi; Manuel de la Torre Juárez (Icarus, 2025)

Challenging the Standard Immunogenicity Assessment Approach: 1-Tiered ADA Testing Strategy in Clinical Trials - Ching-Ha Lai; Mu Chen; Sasha Fraser; Jessica Wang; Sean McAfee; Emma Speaks; Nicholas Simeone; Jacqueline Rodriguez; Colin Stefan; Lisa DeStefano; Chinnasamy Elango; Matthew D. Andisik; et al. (The AAPS Journal, 2024)

High frequency of plastic ingestion in procellariiform seabirds (albatrosses, petrels and shearwaters) in the Southwest Atlantic Ocean - Luciana Gallo; Patricia P. Serafini; Ralph E.T. Vanstreels; Leandro L. Tamini; Cristiane K.M. Kolesnikovas; Alice Pereira; Tatiana Neves; Gabriel D. Nascimento; Lucas S. Rodriguez Pirani; A. Lorena Picone; Rosana M. Romano; C. Karina Alvarez; et al. (Marine Pollution Bulletin, 2024)

Coral-killing and competitive sponges in Nusa Dua, Bali, Indonesia - Dwi Haryanti; Alifalah T. Cahyadi; Fitri F.N. Al Haliim; Hafidza Mahira; Erin Karissa; Anindya Wirasatriya; Pariama Hutasoit; Diah P. Wijayanti; Munasik Munasik; Maria V. Baria-Rodriguez; Ardiansyah D. Puryajati (Regional Studies in Marine Science, 2024)

Deployment-invariant probability of detection characterization for aerial LiDAR methane detection - Michael J. Thorpe; Aaron Kreitinger; Dominic T. Altamura; Cameron D. Dudiak; Bradley M. Conrad; David R. Tyner; Matthew R. Johnson; Jason K. Brasseur; Peter A. Roos; William M. Kunkel; Asa Carre-Burritt; Jerry Abate; et al. (Remote Sensing of Environment, 2024)

Air quality in olive mill wastewater evaporation ponds: Assessment of chemical and microbiological pollutants - G. Viteri; A. Rodríguez; A. Aranda; Y. Díaz de Mera; D. Rodríguez; N. Rodriguez-Fariñas; N. Valiente; G. Belinchón; S. Seseña (Environmental Pollution, 2024)

Competitive ability of three native grass species during establishment - M. C. Scarfó; D. A. Rodriguez; C. Milano; A. Loydi (Plant Ecology, 2024)

Iterative Development of an Interactive Website to Support Shared Decision-Making in Metastatic Breast Cancer - Claire C. Conley; Sophia Cumbo; Jacqueline Chavez Ochoa; Afton Boles; Jennifer D. Rodriguez; Nicole Schwab; David Farrell; Suzan Abduljawad; Claudine Isaacs; Suzanne C. O’Neill (Journal of Cancer Education, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Improving the Nutrition Focused Physical Exam Process to Identify and Address Malnutrition - K. Hung; D. Rodriguez-Brindicci (Journal of the Academy of Nutrition and Dietetics, 2024)

Vacancies engineering in ultrathin porous g-C3N4 tubes for enhanced photocatalytic PMS activation for imidacloprid degradation - Bin Yang; Jiaojiao Zhao; Youpeng Xiong; Cuihua Li; Mei Zhang; Raul D. Rodriguez; Xin Jia (Chemical Engineering Journal, 2024)

The Impact of Microbial Interactions on Ecosystem Function Intensifies Under Stress - Brittni L. Bertolet; Luciana Chavez Rodriguez; José M. Murúa; Alonso Favela; Steven D. Allison (Ecology Letters, 2024)
A major challenge in ecology is to understand how different species interact to determine ecosystem function, particularly in communities with large numbers of co‐occurring species. We use a trait‐based model of microbial litter decomposition to quantify how different taxa impact ecosystem function. Furthermore, we build a novel framework that highlights the interplay between taxon traits and environmental conditions, focusing on their combined influence on community interactions and ecosystem function. Our results suggest that the ecosystem impact of a taxon is driven by its resource acquisition traits and the community functional capacity, but that physiological stress amplifies the impact of both positive and negative interactions. Furthermore, net positive impacts on ecosystem function can arise even as microbes have negative pairwise interactions with other taxa. As communities shift in response to global climate change, our findings reveal the potential to predict the biogeochemical functioning of communities from taxon traits and interactions.

Defining an ageing-related pathology, disease or syndrome: International Consensus Statement - Emma Short; Ian M. Adcock; Bilal Al-Sarireh; Ann Ager; Ramzi Ajjan; Naveed Akbar; Michael A. Akeroyd; Ghada Alsaleh; Ghada Al-Sharbatee; Kambiz Alavian; Winfried Amoaku; Julie Andersen; et al. (GeroScience, 2024)
Around the world, individuals are living longer, but an increased average lifespan does not always equate to an increased health span. With advancing age, the increased prevalence of ageing-related diseases can have a significant impact on health status, functional capacity and quality of life. It is therefore vital to develop comprehensive classification and staging systems for ageing-related pathologies, diseases and syndromes. This will allow societies to better identify, quantify, understand and meet the healthcare, workforce, well-being and socioeconomic needs of ageing populations, whilst supporting the development and utilisation of interventions to prevent or to slow, halt or reverse the progression of ageing-related pathologies. The foundation for developing such classification and staging systems is to define the scope of what constitutes an ageing-related pathology, disease or syndrome. To this end, a consensus meeting was hosted by the International Consortium to Classify Ageing-Related Pathologies (ICCARP), on February 19, 2024, in Cardiff, UK, and was attended by 150 recognised experts. Discussions and voting were centred on provisional criteria that had been distributed prior to the meeting. The participants debated and voted on these. Each criterion required a consensus agreement of ≥ 70% for approval. The accepted criteria for an ageing-related pathology, disease or syndrome were (1) develops and/or progresses with increasing chronological age; (2) should be associated with, or contribute to, functional decline or an increased susceptibility to functional decline and (3) evidenced by studies in humans. Criteria for an ageing-related pathology, disease or syndrome have been agreed by an international consortium of subject experts. These criteria will now be used by the ICCARP for the classification and ultimately staging of ageing-related pathologies, diseases and syndromes.

S13-04 Towards interoperable modelling tools for integrative risk assessment – the PARC model network approach - J. Kruisselbrink; W. de Boer; M. van Lenthe; T. van Voorthuijsen; P. Palmont; L. Rodriguez Martin; D. Devriendt; E. Govarts; M. Carsique; A. Crépet; J. van Klaveren; J. Engel (Toxicology Letters, 2024)

The effect of fluvial avulsion on the Holocene chronostratigraphic record and the agricultural signal of the world's largest coastal lagoonal system - A.S.P. Avila; S.R. Bottezini; D. Diniz; C. Bueno; L. Perez; G. Martínez de la Escalera; C. Piccini; A. Leonhardt; F. Garcia-Rodriguez; J. Weschenfelder (Science of The Total Environment, 2024)

A direct geolocation method for aerial imaging surveys of invasive plants - R. Rodriguez; D. M. Jenkins; J. Leary; R. Perroy (International Journal of Environmental Science and Technology, 2024)

Optimization of LiF dissolution with Al2(SO4)3 and its application to lithium extraction by fluorination of α-spodumene - Gustavo D. Rosales; Alexander C. Resentera; Gretel J. Fino; Eliana G. Pinna; Mario H. Rodriguez (Hydrometallurgy, 2024)

Assessing the nitrogen supply of hairy vetch in a soybean-wheat sequence - Maria P. Rodriguez; Ana J.P. Carcedo; Adrian A. Correndo; Cecilia Crespo; Walter D. Carciochi; Hernan R. Sainz Rozas; Ignacio A. Ciampitti; Pablo A. Barbieri (Field Crops Research, 2024)

Impact of a water restriction on the summer climatic benefits of trees inside an outdoor street canyon scale model - J. Thierry; S. Herpin; R. Levi; D. Canonne; S. Demotes-Mainard; P. Cannavo; D. Lemesle; L. Brialix; F. Rodriguez; P.E. Bournet (Building and Environment, 2024)

Ataxia-telangiectasia in Latin America: clinical features, immunodeficiency, and mortality in a multicenter study - Renan A. Pereira; Ellen O. Dantas; Jessica Loekmanwidjaja; Juliana T. L. Mazzucchelli; Carolina S. Aranda; Maria E. G. Serrano; Elisabeth A. De La Cruz Córdoba; Liliana Bezrodnik; Ileana Moreira; Janaira F. S. Ferreira; Vera M. Dantas; Valéria S. F. Sales; et al. (Immunologic Research, 2024)

Towards solving the reproducibility crisis in surface-enhanced Raman spectroscopy-based pesticide detection - Andrey Averkiev; Raul D. Rodriguez; Maxim Fatkullin; Anna Lipovka; Bin Yang; Xin Jia; Olfa Kanoun; Evgeniya Sheremet (Science of The Total Environment, 2024)

Pioneering minimum liquid discharge desalination: A pilot study in Lampedusa Island - C. Morgante; F. Vassallo; C. Cassaro; G. Virruso; D. Diamantidou; N. Van Linden; A. Trezzi; C. Xenogianni; R. Ktori; M. Rodriguez; G. Scelfo; S. Randazzo; et al. (Desalination, 2024)

Integrated organismal responses induced by projected levels of CO 2 and temperature exposures in the early life stages of lake sturgeon - Luke D. Belding; Matt J. Thorstensen; Alex R. Quijada‐Rodriguez; William S. Bugg; Gwangseok R. Yoon; Alison R. Loeppky; Garrett J. P. Allen; Alexandra N. Schoen; Madison L. Earhart; Catherine Brandt; Jennifer L. Ali; Dirk Weihrauch; et al. (Molecular Ecology, 2024)
Atmospheric CO 2 and temperature are rising concurrently, and may have profound impacts on the transcriptional, physiological and behavioural responses of aquatic organisms. Further, spring snowmelt may cause transient increases of p CO 2 in many freshwater systems. We examined the behavioural, physiological and transcriptomic responses of an ancient fish, the lake sturgeon ( Acipenser fulvescens ) to projected levels of warming and p CO 2 during its most vulnerable period of life, the first year. Specifically, larval fish were raised in either low (16°C) or high (22°C) temperature, and/or low (1000 μatm) or high (2500 μatm) p CO 2 in a crossed experimental design over approximately 8 months. Following overwintering, lake sturgeon were exposed to a transient increase in p CO 2 of 10,000 μatm, simulating a spring melt based on data in freshwater systems. Transcriptional analyses revealed potential connections to otolith formation and reduced growth in fish exposed to high p CO 2 and temperature in combination. Network analyses of differential gene expression revealed different biological processes among the different treatments on the edges of transcriptional networks. Na + /K + ‐ATPase activity increased in fish not exposed to elevated p CO 2 during development, and mRNA abundance of the β subunit was most strongly predictive of enzyme activity. Behavioural assays revealed a decrease in total activity following an acute CO 2 exposure. These results demonstrate compensatory and compounding mechanisms of p CO 2 and warming dependent on developmental conditions in lake sturgeon. Conserved elements of the cellular stress response across all organisms provide key information for how other freshwater organisms may respond to future climate change.

A Bayesian Multiplex Graph Classifier of Functional Brain Connectivity Across Diverse Tasks of Cognitive Control - Sharmistha Guha; Jose Rodriguez-Acosta; Ivo D. Dinov (Neuroinformatics, 2024)

Spatially heterogeneous discharge of glacial meltwater to drainages surrounding the ablating Coropuna ice cap, Peruvian Andes - Elizabeth J. Olson; Lisa R. Welp; Marty D. Frisbee; Sebastián A. Zúñiga Medina; Odiney Alvarez-Campos; Wendy R. Roque Quispe; Carol I. Salazar Mamani; Midhuar R. Arenas Carrión; José Diaz Rodriguez; Juan Manuel Jara Gonzalez; Alexander Ccanccapa-Cartagena; Chad T. Jafvert (Hydrological Sciences Journal, 2024)

Total CO2 budget estimate and degassing dynamics for an active stratovolcano: Turrialba Volcano, Costa Rica - Kate M. Nelson; Christofer Jiménez; Chad D. Deering; Maarten J. de Moor; Joshua M. Blackstock; Stephen P. Broccardo; Florian M. Schwandner; Joshua B. Fisher; Snehamoy Chatterjee; Guillermo Alvarado Induni; Alejandro Rodriguez; Doménicca Guillén Pachacama; et al. (Journal of Volcanology and Geothermal Research, 2024)

Increases in regional brain volume across two native South American male populations - Nikhil N. Chaudhari; Phoebe E. Imms; Nahian F. Chowdhury; Margaret Gatz; Benjamin C. Trumble; Wendy J. Mack; E. Meng Law; M. Linda Sutherland; James D. Sutherland; Christopher J. Rowan; L. Samuel Wann; Adel H. Allam; et al. (GeroScience, 2024)
Industrialized environments, despite benefits such as higher levels of formal education and lower rates of infections, can also have pernicious impacts upon brain atrophy. Partly for this reason, comparing age-related brain volume trajectories between industrialized and non-industrialized populations can help to suggest lifestyle correlates of brain health. The Tsimane, indigenous to the Bolivian Amazon, derive their subsistence from foraging and horticulture and are physically active. The Moseten, a mixed-ethnicity farming population, are physically active but less than the Tsimane. Within both populations ( N = 1024; age range = 46–83), we calculated regional brain volumes from computed tomography and compared their cross-sectional trends with age to those of UK Biobank (UKBB) participants ( N = 19,973; same age range). Surprisingly among Tsimane and Moseten (T/M) males, some parietal and occipital structures mediating visuospatial abilities exhibit small but significant increases in regional volume with age. UKBB males exhibit a steeper negative trend of regional volume with age in frontal and temporal structures compared to T/M males. However, T/M females exhibit significantly steeper rates of brain volume decrease with age compared to UKBB females, particularly for some cerebro-cortical structures (e.g., left subparietal cortex). Across the three populations, observed trends exhibit no interhemispheric asymmetry. In conclusion, the age-related rate of regional brain volume change may differ by lifestyle and sex. The lack of brain volume reduction with age is not known to exist in other human population, highlighting the putative role of lifestyle in constraining regional brain atrophy and promoting elements of non-industrialized lifestyle like higher physical activity.

Trophic ecology of sympatric sea turtles in the tropical Atlantic coast of Brazil - Moises F. Bezerra; Cesar A. Barrios-Rodriguez; Carlos E. Rezende; Melania C. López-Castro; Luiz D. Lacerda (Marine Environmental Research, 2024)

Holocene organic matter composition in relation to relative sea level stands and associated morphometric changes of a lagoonal system - V. Carvalho; L. Gonzalez; C. Bueno; C. Segura; S.R. Bottezini; A. Leonhardt; D. Diniz; P. Dentzien-Dias; L. Perez; H. Evangelista; M.V. Licínio; H. Inda; et al. (Marine Geology, 2024)

Possibly seismically triggered avalanches after the S1222a Marsquake and S1000a impact event - A. Lucas; I.J. Daubar; M. Le Teuff; C. Perrin; T. Kawamura; L. Posiolova; P. Lognonné; S. Rodriguez; D. Giardini; G. Sainton; A. Mangeney; A. McEwen (Icarus, 2024)

Enzymatic metal oxide/nanoparticle heterojunctions with mutually reinforced bifunctional chemotherapies for combating drug-resistant bacteria - Qian Zhou; Ting Wang; Zhenyu Xing; Raul D. Rodriguez; Liang Cheng; Yang Gao; Qiu Chen; Chong Cheng (Chemical Engineering Journal, 2024)

One hundred and six years of change in a S onoran D esert plant community: Impact of climate anomalies and trends in species sensitivities - Charlotte Brown; Susana Rodriguez Buritica; Deborah E. Goldberg; Frank Reichenbacher; D. Lawrence Venable; Robert H. Webb; Benjamin T. Wilder (Ecology, 2024)
A major restriction in predicting plant community response to future climate change is a lack of long‐term data needed to properly assess species and community response to climate and identify a baseline to detect climate anomalies. Here, we use a 106‐year dataset on a Sonoran Desert plant community to test the role of extreme temperature and precipitation anomalies on community dynamics at the decadal scale and over time. Additionally, we tested the climate sensitivity of 39 desert plant species and whether sensitivity was associated with growth form, longevity, geographic range, or local dominance. We found that desert plant communities had shifted directionally over the 106 years, but the climate had little influence on this directional change primarily due to nonlinear shifts in precipitation anomalies. Decadal‐scale climate had the largest impact on species richness, species relative density, and total plant cover, explaining up to 26%, 45%, and 55% of the variance in each, respectively. Drought and the interaction between the frequency of freeze events and above‐average summer precipitation were among the most influential climate factors. Increased drought frequency and wetter periods with frequent freeze events led to larger reductions in total plant cover, species richness, and the relative densities of dominant subshrubs Ambrosia deltoidea and Encelia farinosa . More than 80% of the tested species were sensitive to climate, but sensitivity was not associated with a species' local dominance, longevity, geographic range, or growth form. Some species appear to exhibit demographic buffering, where when they have a higher sensitivity to drought, they also tend to have a higher sensitivity to favorable (i.e., wetter and hotter) conditions. Overall, our results suggest that, while decadal‐scale climate variation substantially impacts these desert plant communities, directional change in temperature over the last century has had little impact due to the relative importance of precipitation and drought. With projections of increased drought in this region, we may see reductions in total vegetation cover and species richness due to the loss of species, possibly through a breakdown in their ability to demographically buffer climatic variation, potentially changing community dynamics through a change in facilitative and competitive processes.

Analysis of an optical imaging system prototype for autonomously monitoring zooplankton in an aquaculture facility - M.N. Bowman; R.A. McManamay; A. Rodriguez Perez; G. Hamerly; W. Arnold; E. Steimle; K. Kramer; B. Norris; D. Prangnell; M. Matthews (Aquacultural Engineering, 2024)

Embryo-maternal communication mediated by extracellular vesicles in the early stages of embryonic development is modified by in vitro conditions - C. Aguilera; Y.S. Wong; M.A. Gutierrez-Reinoso; A.E. Velásquez; B. Melo-Báez; J. Cabezas; D. Caamaño; F. Navarrete; F.O. Castro; L.l. Rodriguez-Alvarez (Theriogenology, 2024)

Understanding the differences between car and motorcycle ownership. The case of Bogotá, Colombia - Alvaro Rodriguez-Valencia; J. de D. Ortúzar; Santiago Mesa-Garcia (Journal of Transport Geography, 2024)

Impact of Drought on Ecohydrology of Southern California Grassland and Shrubland - Luciana Chavez Rodriguez; Scot Parker; Nicole M. Fiore; Steven D. Allison; Michael L. Goulden (Ecosystems, 2024)
Through their rooting profiles and water demands, plants affect the distribution of water in the soil profile. Simultaneously, soil water content controls plant development and interactions within and between plant communities. These plant-soil water feedbacks might vary across plant communities with different rooting depths and species composition. In semiarid environments, understanding these differences will be essential to predict how ecosystems will respond to drought, which may become more frequent and severe with climate change. In this study, we tested how plant-soil water feedbacks responded to drought in two contrasting ecosystem types—grassland and shrubland—in the coastal foothills of southern California. During years 5–8 of an ongoing precipitation manipulation experiment, we measured changes in plant communities and soil moisture up to 2 m depth. We observed different water use patterns in grassland and shrubland communities with distinct plant functional types and water use strategies. Drought treatment did not affect perennial, deep-rooted shrubs because they could access deep soil water pools. However, mid-rooted shrubs were sensitive to drought and experienced decreased productivity and die-off. As a result, water content actually increased with drought at soil depths from 50–150 cm. In grassland, biomass production by annual species, including annual grasses and forbs, declined with drought, resulting in lower water uptake from the surface soil layer. An opportunistic “live fast, die young“ life strategy allowed these species to recover quickly once water availability increased. Our results show how drought interacts with plant community composition to affect the soil water balance of semiarid ecosystems, information that could be integrated into global scale models.

Regional differences in Hg contents in the liver and muscle of the green turtle (Chelonia mydas) from three foraging grounds in Northeast Brazil - Paul Verzele; César B. Rodriguez; Moisés F. Bezerra; Luiz D. Lacerda (Environmental Science and Pollution Research, 2023)

Trauma-Informed Care Training for Dietetic Interns Improves Attitudes Toward Women Who Have Experienced Trauma - Nancy Rodriguez; Diana M. Gonzales-Pacheco; Laura D. Byham-Gray; Pamela Rothpletz-Puglia (Journal of Nutrition Education and Behavior, 2023)

Assessing the energy recovery potential at district metered areas inlets of water supply systems: A Spanish case study - Ana Fernández-Guillamón; Francisco Javier Pérez de la Cruz; Borja Valverde-Pérez; Pedro D. Martínez-Solano; Antonio Vigueras-Rodriguez (Journal of Environmental Management, 2023)

From lab to table: Expanding gastronomic possibilities with fermentation using the edible fungus Neurospora intermedia - Vayu Maini Rekdal; Nabila Rodriguez-Valeron; Mikel Olaizola Garcia; Diego Prado Vásquez; Pia M. Sörensen; Rasmus Munk; Jay D. Keasling (International Journal of Gastronomy and Food Science, 2023)

Simultaneous improvement of grain yield and grain protein concentration in durum wheat by using association tests and weighted GBLUP - Salvatore Esposito; Paolo Vitale; Francesca Taranto; Sergio Saia; Ivano Pecorella; Nunzio D’Agostino; Monica Rodriguez; Vincenzo Natoli; Pasquale De Vita (Theoretical and Applied Genetics, 2023)

Detection of SARS-CoV-2 in high-efficiency particulate air (HEPA) filters of low-cost air purifiers in community-based organizations - Rachel D. Clarke; Nana Aisha Garba; Manuel A. Barbieri; Leonardo Acuna; Marianna Baum; Maribel Saad Rodriguez; Hansel Frias; Paulina Saldarriaga; Troy Stefano; Kalai Mathee; Giri Narasimhan; David R. Brown (Environmental Monitoring and Assessment, 2023)
This study aims to investigate the presence of SARS-CoV-2 in public spaces and assess the utility of inexpensive air purifiers equipped with high-efficiency particulate air (HEPA) filters for viral detection. Samples were collected from six community-based organizations in underserved minority neighborhoods in Northwest Miami, Florida, from February to May 2022. Reverse transcription–quantitative polymerase chain reaction (RT-qPCR) was used to detect SARS-CoV-2 in air purifier filters and surface swabs. Among 32 filters tested, three yielded positive results, while no positive surface swabs were found. Notably, positive samples were obtained exclusively from child daycare centers. These findings highlight the potential for airborne transmission of SARS-CoV-2 in indoor air, particularly in child daycare centers. Moreover, the study demonstrates the effectiveness of readily available HEPA filters in detecting the virus. Improving indoor ventilation and implementing air filtration systems are crucial in reducing COVID-19 transmission where people gather. Air filtration systems incorporating HEPA filters offer a valuable approach to virus detection and reducing transmission risks. Future research should explore the applicability of this technology for early identification and mitigation of viral outbreaks.

Adsorption of azithromycin in agricultural soils of the Bogotá savanna, Colombia - Martha Cristina Bustos-López; D. Crispin-Rodriguez; María P. Martínez-Polanco; R. Cante-Ríos (Science of The Total Environment, 2023)

Smoking, blood DNA methylation sites and lung cancer risk - Arce Domingo-Relloso; Roby Joehanes; Zulema Rodriguez-Hernandez; Lies Lahousse; Karin Haack; M. Daniele Fallin; Miguel Herreros-Martinez; Jason G. Umans; Lyle G. Best; Tianxiao Huan; Chunyu Liu; Jiantao Ma; et al. (Environmental Pollution, 2023)

A randomised trial to assess fluid and electrolyte balance responses following ingestion of different beverages in young and older men - Nidia Rodriguez-Sanchez; Stuart D. R. Galloway (European Journal of Applied Physiology, 2023)
Background Older adults are susceptible to dehydration and fluid overload due to a reduced ability to maintain homeostatic control of fluid and electrolyte balance. Purpose To assess fluid and electrolyte balance responses in young and older men following ingestion of commonly consumed beverages differing in composition. Methods 12 young and 11 older men were recruited. Euhydrated body mass was recorded. Participants consumed 1L (250 ml every 15 min) of water, fruit juice, a sports drink or low-fat milk in a randomized cross-over design. Urine and blood samples were obtained before and after the drinking period and every hour thereafter for 3-h. Samples were used to determine osmolality, electrolytes (Na + and K + ), water clearance, and glomerular filtration rate. Results Free water clearance was significantly higher in Young than Older at 1 and 2 h after the ingestion of W and S (p < 0.05). Net Na + and K + balance were not different between Young and Older (p = 0.91 and p = 0.65) adults, respectively. At 3 h Na + balance was negative after ingesting water and fruit juice, but neutral after sport drink and milk. Net K + balance was neutral at 3 h after ingesting milk, but negative after water, fruit juice and sport drink. Conclusions Milk was retained longer than other beverages in Young, but not in Older, despite similar net electrolyte balance responses. Older had higher fluid retention in the first 2 h after the ingestion of all beverages, except for milk when compared to Young, indicating an age-related loss of ability to regulate fluid balance under current study conditions.

LP-51: Determining of a broad range of organic chemicals in seminal plasma through an innovative LC-HRMS-based methodology suitable for target and non-target analysis - E. Sánchez-Resino; M. Marquès; D. Gutiérrez-Martín; E. Restrepo-Montes; M. Á. Martínez-Rodriguez; A. Salas-Huetos; N. Babio; J. Salas-Salvadó; J.L. Domingo; R. Gil-Solsona; P. Gago-Ferrero (Toxicology Letters, 2023)

Evaluation of the susceptibility of Tritrichomonas foetus to extracts of Lantana camara (Verbenaceae) by flow cytometry - LA López; ME Luque; MB Rivero; ME Abdala; PG Carranza; BE Luna; D Di Lullo; BJ Volta; SA Rodriguez; FD Rivero (Veterinary Research Communications, 2023)

Constructing BiOBr/TiO2 heterostructure nanotubes for enhanced adsorption/photocatalytic performance - Sheng-Zhe Zhao; Yun Lu; Ran Lu; Yong-Da Hu; Raul D. Rodriguez; Jin-Ju Chen (Journal of Water Process Engineering, 2023)

Radio- and stable carbon isotope analysis reveals minimal assimilation of petrogenic carbon into an oligotrophic freshwater food web after experimental spills of diluted bitumen - Stephanie D. Graves; Johanna J. Mason; Jose Luis Rodriguez-Gil; Jonathan Y. Séguin; Jules M. Blais; Mark L. Hanson; Bruce P. Hollebone; Vince P. Palace; Ian Clark; Leah Cundall; Daniel Layton-Matthews; Matthew I. Leybourne; et al. (Chemosphere, 2023)

Use-up day and flexible recipes: Reducing household food waste by helping families prepare food they already have - A. Cooper; R. Lion; O.E. Rodriguez-Sierra; P. Jeffrey; D. Thomson; K. Peters; L. Christopher; M.J.H. Zhu; L. Wistrand; P. van der Werf; E. van Herpen (Resources, Conservation and Recycling, 2023)

The interaction between liver cirrhosis, infection by Streptococcus bovis, and colon cancer - Juan Corredoira; Enrique Miguez; Lara María Mateo; Ricardo Fernández-Rodríguez; José Francisco García-Rodríguez; Alexandre Pérez-González; Ana Sanjurjo; María Victoria Pulian; Blanca Ayuso-García; M. Serrano; M. J. Jove; P. Alonso; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2023)

Observation of large scale precursor correlations between cosmic rays and earthquakes with a periodicity similar to the solar cycle - P. Homola; V. Marchenko; A. Napolitano; R. Damian; R. Guzik; D. Alvarez-Castillo; S. Stuglik; O. Ruimi; O. Skorenok; J. Zamora-Saa; J.M. Vaquero; T. Wibig; et al. (Journal of Atmospheric and Solar-Terrestrial Physics, 2023)

Recent growth increase in endemic Juglans boliviana from the tropical Andes - Rose C. Oelkers; Laia Andreu-Hayles; Rosanne D’Arrigo; Arturo Pacheco-Solana; Milagros Rodriguez-Caton; Alfredo Fuentes; Guaciara M. Santos; Ernesto Tejedor; M. Eugenia Ferrero; Carla Maldonado (Dendrochronologia, 2023)

Tree crown traits and planting context contribute to reducing urban heat - Mahmuda Sharmin; Mark G. Tjoelker; Sebastian Pfautsch; Manuel Esperon-Rodriguez; Paul D. Rymer; Sally A. Power (Urban Forestry & Urban Greening, 2023)

Urban tree inventories as a tool to assess tree growth and failure: The case for Australian cities - Manuel Esperon-Rodriguez; Desi Quintans; Paul D. Rymer (Landscape and Urban Planning, 2023)

Comparison of the 7-day CO-Synch and 8-day estradiol-based protocols for estrus synchronization and timed artificial insemination in suckled Bos taurus cows - Alejandro M. Rodriguez; Sebastian Maresca; Sebastian López-Valiente; María G. Bilbao; Karen D. Moran; Julián A. Bartolome; Scott L. Pratt; Nathan M. Long (Theriogenology, 2023)

Kisspeptin as potential biomarker of environmental chemical mixture effect on reproductive hormone profile: A pilot study in adolescent males - Andrea Rodriguez-Carrillo; Sylvie Remy; Shereen Cynthia D'Cruz; Elena Salamanca-Fernandez; Fernando Gil; Pablo Olmedo; Vicente Mustieles; Fernando Vela-Soria; Kirsten Baken; Nicolás Olea; Fátima Smagulova; Mariana F. Fernandez; et al. (Science of The Total Environment, 2023)

Direct Z-scheme g-C3N4/TiO2 heterojunction porous nanotubes: An ingenious synthesis strategy to enhance photocatalytic activity - Sheng-Zhe Zhao; Ran Lu; Yi Yang; Yun Lu; Raul D. Rodriguez; Jin-Ju Chen (Journal of Environmental Chemical Engineering, 2023)

Lithium fluoride dissolution in sulfuric acid solution: Optimization and application in the extraction of lithium from fluorinated α-spodumene - Alexander C. Resentera; Gustavo D. Rosales; Marcelo R. Esquivel; Mario H. Rodriguez (Hydrometallurgy, 2023)

PFAS levels and exposure determinants in sensitive population groups - L. Fábelová; A. Beneito; M. Casas; A. Colles; L. Dalsager; E. Den Hond; C. Dereumeaux; K. Ferguson; L. Gilles; E. Govarts; A. Irizar; M.J. Lopez Espinosa; et al. (Chemosphere, 2023)

Global assessment of chemical quality of drinking water: The case of trihalomethanes - Cristina M Villanueva; Iro Evlampidou; Fathelrahman Ibrahim; Carolina Donat-Vargas; Antonia Valentin; Anca-Maria Tugulea; Shinya Echigo; Dragana Jovanovic; Albert T Lebedev; Mildred Lemus-Pérez; Manuel Rodriguez-Susa; Arben Luzati; et al. (Water Research, 2023)

Inkjet-printed MoS2-based 3D-structured electrocatalysts on Cu films for ultra-efficient hydrogen evolution reaction - Pei-Zhen Li; Na Chen; Ammar Al-Hamry; Evgeniya Sheremet; Ran Lu; Yi Yang; Olfa Kanoun; Reinhard R. Baumann; Raul D. Rodriguez; Jin-Ju Chen (Chemical Engineering Journal, 2023)

The Challenges of Characterizing the Zooplankton Community Response Following Simulated Spills of Diluted Bitumen into Boreal Lake Limnocorrals - T. A. Black; M. J. Paterson; L. Timlick; J. Cederwall; J. M. Blais; B. Hollebone; D. M. Orihel; V. P. Palace; J. L. Rodriguez-Gil; M. L. Hanson (Bulletin of Environmental Contamination and Toxicology, 2023)

PFAS levels and determinants of variability in exposure in European teenagers – Results from the HBM4EU aligned studies (2014–2021) - D. Richterová; E. Govarts; L. Fábelová; K. Rausová; L. Rodriguez Martin; L. Gilles; S. Remy; A. Colles; L. Rambaud; M. Riou; C. Gabriel; D. Sarigiannis; et al. (International Journal of Hygiene and Environmental Health, 2023)

The role of copper crystallization and segregation toward enhanced methanol synthesis via CO2 hydrogenation over CuZrO2 catalysts: A combined experimental and computational study - Francielle C.F. Marcos; Raphael S. Alvim; Lili Lin; Luis E. Betancourt; Davi D. Petrolini; Sanjaya D. Senanayake; Rita M.B. Alves; José M. Assaf; Jose A. Rodriguez; Reinaldo Giudici; Elisabete M. Assaf (Chemical Engineering Journal, 2023)

Oral Medicine Experience and Attitudes Toward Oral Cancer: An Evaluation of Dentists Working in Primary Health Care - Jéssica Rodriguez Strey; Michelle Roxo-Gonçalves; Bianca Dutra Guzenski; Marco Antonio Trevizani Martins; Juliana Romanini; Maria Antonia Zancanaro de Figueiredo; Otávio Pereira D’Ávila; Marcelo Rodrigues Gonçalves; Roberto Nunes Umpierre; Erno Harzheim; Laura de Campos Hildebrand; Vinicius Coelho Carrard (Journal of Cancer Education, 2022)

A novel series of pyrazole derivatives toward biological applications: experimental and conceptual DFT characterization - Pedro D. Ortiz; Judith Castillo-Rodriguez; Jorge Tapia; Ximena Zarate; Gabriel A. Vallejos; Vanesa Roa; Elies Molins; Carlos Bustos; Eduardo Schott (Molecular Diversity, 2022)

Correction: Amphibian phylogenetic diversity in the face of future climate change: not so good news for the Chilean biodiversity hotspot - Leonardo J. Rodriguez; Olga A. Barbosa; Claudio Azat; Mario Alvarado-Rybak; Claudio Correa; Marco A. Méndez; Felipe N. Moreno-Gómez; Felipe E. Rabanal; Marcela A. Vidal; Nelson A. Velásquez; Leonardo D. Bacigalupe (Biodiversity and Conservation, 2022)

Amphibian phylogenetic diversity in the face of future climate change: not so good news for the chilean biodiversity hotspot - Leonardo J. Rodriguez; Olga A. Barbosa; Claudio Azat; Mario Alvarado-Rybak; Claudio Correa; Marco A. Méndez; Felipe N. Moreno-Gómez; Felipe E. Rabanal; Marcela A. Vidal; Nelson A. Velásquez; Leonardo D. Bacigalupe (Biodiversity and Conservation, 2022)

The Colombian geochronological database (CGD) - Andres F. Rodriguez-Corcho; Yamirka Rojas-Agramonte; Johana A. Barrera-Gonzalez; Maria P. Marroquin-Gomez; Sarah Bonilla-Correa; David Izquierdo-Camacho; Sofia M. Delgado-Balaguera; David Cartwright-Buitrago; Maria D. Muñoz-Granados; William G. Carantón-Mateus; Alejandro Corrales-García; Andrés F. Laverde-Martinez; et al. (International Geology Review, 2022)

Novel Fusarium wilt resistance genes uncovered in natural and cultivated strawberry populations are found on three non-homoeologous chromosomes - Dominique D. A. Pincot; Mitchell J. Feldmann; Michael A. Hardigan; Mishi V. Vachev; Peter M. Henry; Thomas R. Gordon; Marta Bjornson; Alan Rodriguez; Nicolas Cobo; Randi A. Famula; Glenn S. Cole; Gitta L. Coaker; et al. (Theoretical and Applied Genetics, 2022)
Key Message Several Fusarium wilt resistance genes were discovered, genetically and physically mapped, and rapidly deployed via marker-assisted selection to develop cultivars resistant to Fusarium oxysporum f. sp. fragariae , a devastating soil-borne pathogen of strawberry . Abstract Fusarium wilt, a soilborne disease caused by Fusarium oxysporum f. sp. fragariae , poses a significant threat to strawberry ( Fragaria $$×$$ × ananassa ) production in many parts of the world. This pathogen causes wilting, collapse, and death in susceptible genotypes. We previously identified a dominant gene ( FW1 ) on chromosome 2B that confers resistance to race 1 of the pathogen, and hypothesized that gene-for-gene resistance to Fusarium wilt was widespread in strawberry. To explore this, a genetically diverse collection of heirloom and modern cultivars and octoploid ecotypes were screened for resistance to Fusarium wilt races 1 and 2. Here, we show that resistance to both races is widespread in natural and domesticated populations and that resistance to race 1 is conferred by partially to completely dominant alleles among loci ( FW1 , FW2 , FW3 , FW4 , and FW5 ) found on three non-homoeologous chromosomes (1A, 2B, and 6B). The underlying genes have not yet been cloned and functionally characterized; however, plausible candidates were identified that encode pattern recognition receptors or other proteins known to confer gene-for-gene resistance in plants. High-throughput genotyping assays for SNPs in linkage disequilibrium with FW1 - FW5 were developed to facilitate marker-assisted selection and accelerate the development of race 1 resistant cultivars. This study laid the foundation for identifying the genes encoded by FW1-FW5 , in addition to exploring the genetics of resistance to race 2 and other races of the pathogen, as a precaution to averting a Fusarium wilt pandemic.

Extinct groundwater discharge locality in the Eldorado Valley; eastern Mojave Desert, Nevada, USA - Douglas B. Sims; Amanda C. Hudson; John E. Keller; Paul McBurnett; David Ferrari; Giavanna M. Fernandez; Juan Garcia-Hernandez; Bailey D. Kesl; Flavio W. Rodriguez; Sean G. Torres (Journal of Sedimentary Environments, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Correction to: Pterocarpus marsupium extract extends replicative lifespan in budding yeast - Mitchell B. Lee; Michael G. Kiflezghi; Mitsuhiro Tsuchiya; Brian Wasko; Daniel T. Carr; Priya A. Uppal; Katherine A. Grayden; Yordanos C. Elala; Tu Anh Nguyen; Jesse Wang; Priya Rastogi; Sunny Nguyen; et al. (GeroScience, 2022)

Experimental and Computational Models of Transport of Galectin-3 Through Glycosylated Matrix - Janny Piñeiro-Llanes; Camille D. Rodriguez; Shaheen A. Farhadi; Gregory A. Hudalla; Malisa Sarntinoranont; Chelsey S. Simmons (Annals of Biomedical Engineering, 2022)

Globally, tree fecundity exceeds productivity gradients - Valentin Journé; Robert Andrus; Marie‐Claire Aravena; Davide Ascoli; Roberta Berretti; Daniel Berveiller; Michal Bogdziewicz; Thomas Boivin; Raul Bonal; Thomas Caignard; Rafael Calama; Jesús Julio Camarero; et al. (Ecology Letters, 2022)
Lack of tree fecundity data across climatic gradients precludes the analysis of how seed supply contributes to global variation in forest regeneration and biotic interactions responsible for biodiversity. A global synthesis of raw seedproduction data shows a 250‐fold increase in seed abundance from cold‐dry to warm‐wet climates, driven primarily by a 100‐fold increase in seed production for a given tree size. The modest (threefold) increase in forest productivity across the same climate gradient cannot explain the magnitudes of these trends. The increase in seeds per tree can arise from adaptive evolution driven by intense species interactions or from the direct effects of a warm, moist climate on tree fecundity. Either way, the massive differences in seed supply ramify through food webs potentially explaining a disproportionate role for species interactions in the wet tropics.

Revealing diagnostic characters through morphological evolution in cleptoparasitic spider wasps (Hymenoptera, Pompilidae, Ceropales ) - Cecilia Waichert; Juanita Rodriguez; Arkady S. Lelej; Carol D. von Dohlen; James P. Pitts (Zoologica Scripta, 2022)
Spider wasps (Hymenoptera: Pompilidae) cleptoparasites, such as Ceropales Latreille, have evolved the ability to steal the spiders from other pompilids. This behaviour is often observed with morphological adaptations that might mislead taxonomic decisions due to convergence. For instance, four subgenera, Bifidoceropales Wolf, Ceropales s. str., Hemiceropales Wolf and Priesnerius Móczár and six species‐groups are recognized within Ceropales ; all with doubtful identification. We studied species of Ceropales in light of molecular and morphological characters to delimit lineages and to test the applicability of morphological traits in diagnosing them. We used the molecular nuclear markers long‐wavelength rhodopsin and 28S ribosomal RNA, and the mitochondrial Cytochrome C Oxidase I available at Genebank to reconstruct Bayesian and maximum likelihood phylogenetic trees. Our results disagree with the current subgeneric classification. We found that fore wing venation and the shape of the female posterior metasomal segments are key characters to differentiate lineages. We discuss morphological evolution of the sting apparatus using ancestral state reconstructions; and we propose Bifidoceropales as a junior subjective synonym of Ceropales s. str., whereas Priesnerius , stat. resurr. and Hemiceropales are redefined based on male and female morphological traits. This study raises important concerns, from the validity of diagnostic characters currently used to identify cleptoparasite spider wasps—and taxa with habitat constraints leading to homoplasies. Taxonomy can benefit from the reconstruction of ancestral traits by revealing reliable diagnostic characters. Moreover, our investigation provides a framework for evolutionary studies on hymenopteran cleptoparasitoids and sets the basis for future phylogenomic investigations on Ceropales by opening new perspectives for taxonomic acts and guiding taxonomic sampling efforts.

Development of In Vitro Dissolution Testing Methods to Simulate Fed Conditions for Immediate Release Solid Oral Dosage Forms - Timothy R. Lex; Jason D. Rodriguez; Lei Zhang; Wenlei Jiang; Zongming Gao (The AAPS Journal, 2022)

Phenotypic responses in fish behaviour narrow as climate ramps up - Almendra Rodriguez-Dominguez; Sean D. Connell; Ericka O. C. Coni; Minami Sasaki; David J. Booth; Ivan Nagelkerken (Climatic Change, 2022)
Natural selection alters the distribution of phenotypes as animals adjust their behaviour and physiology to environmental change. We have little understanding of the magnitude and direction of environmental filtering of phenotypes, and therefore how species might adapt to future climate, as trait selection under future conditions is challenging to study. Here, we test whether climate stressors drive shifts in the frequency distribution of behavioural and physiological phenotypic traits (17 fish species) at natural analogues of climate change (CO 2 vents and warming hotspots) and controlled laboratory analogues (mesocosms and aquaria). We discovered that fish from natural populations (4 out of 6 species) narrowed their phenotypic distribution towards behaviourally bolder individuals as oceans acidify, representing loss of shyer phenotypes. In contrast, ocean warming drove both a loss (2/11 species) and gain (2/11 species) of bolder phenotypes in natural and laboratory conditions. The phenotypic variance within populations was reduced at CO 2 vents and warming hotspots compared to control conditions, but this pattern was absent from laboratory systems. Fishes that experienced bolder behaviour generally showed increased densities in the wild. Yet, phenotypic alterations did not affect body condition, as all 17 species generally maintained their physiological homeostasis (measured across 5 different traits). Boldness is a highly heritable trait that is related to both loss (increased mortality risk) and gain (increased growth, reproduction) of fitness. Hence, climate conditions that mediate the relative occurrence of shy and bold phenotypes may reshape the strength of species interactions and consequently alter fish population and community dynamics in a future ocean.

Threatened Andean bears are negatively affected by human disturbance and free-ranging cattle in a protected area in northwest Peru - Francis Aurich-Rodriguez; Renzo P. Piana; Robyn D. Appleton; A. Cole Burton (Mammalian Biology, 2022)

“Right diet for the right person”: a focus group study of nutritionist-dietitians’ perspectives on nutritional genomics and gene-based nutrition advice - Jacus S. Nacis; Marilou R. Galang; Jason Paolo H. Labrador; Milflor S. Gonzales; Aurora Maria Francesca D. Dablo; Diana Glades A. Domalanta-Ronquillo; Victor Franco J. Alfonso; Idelia G. Glorioso; Marietta P. Rodriguez (Journal of Community Genetics, 2022)
Advances in nutritional genomics are intended to revolutionize nutrition practice. A basic understanding of nutritional genomics among nutritionist-dietitians is critical for such advancements to occur. As a precedent to the development and integration of gene-based nutrition advice, this study aimed to assess hospital-based nutritionist-dietitians’ perceptions of nutritional genomics. A total of ten focus group discussions (FGDs) with sixty-one registered nutritionist-dietitians (RNDs) from hospitals in the National Capital Region (NCR), Philippines, were conducted from October to November 2019. Data were collected using a pretested semistructured discussion guide, and thematic analysis was subsequently performed. Diverging perceptions about nutritional genomics were noted among the FGD participants. Five themes emerged relating to the enablers and barriers of gene-based nutrition advice: training and capacity building, the extent of information to be disclosed, cost, ethical considerations, and government support. Themes related to the desired features of the gene-based nutrition advice included being consent-driven, cost-effective, technology-oriented, and guided by standards. The results of this study suggest that training and continued learning will equip RNDs to provide nutrition advice based on genetic information. However, other factors, such as cost and ethical considerations, are critical dimensions that need to be acknowledged and addressed before integrating gene-based advice into nutrition practice.

A Comprehensive, FAIR File Format for Neuroanatomical Structure Modeling - A. E. Sullivan; S. J. Tappan; P. J. Angstman; A. Rodriguez; G. C. Thomas; D. M. Hoppes; M. A. Abdul-Karim; M. L. Heal; Jack R. Glaser (Neuroinformatics, 2022)
With advances in microscopy and computer science, the technique of digitally reconstructing, modeling, and quantifying microscopic anatomies has become central to many fields of biological research. MBF Bioscience has chosen to openly document their digital reconstruction file format, the Neuromorphological File Specification, available at www.mbfbioscience.com/filespecification (Angstman et al., 2020). The format, created and maintained by MBF Bioscience, is broadly utilized by the neuroscience community. The data format’s structure and capabilities have evolved since its inception, with modifications made to keep pace with advancements in microscopy and the scientific questions raised by worldwide experts in the field. More recent modifications to the neuromorphological file format ensure it abides by the Findable, Accessible, Interoperable, and Reusable (FAIR) data principles promoted by the International Neuroinformatics Coordinating Facility (INCF; Wilkinson et al., Scientific Data, 3 , 160018,, 2016). The incorporated metadata make it easy to identify and repurpose these data types for downstream applications and investigation. This publication describes key elements of the file format and details their relevant structural advantages in an effort to encourage the reuse of these rich data files for alternative analysis or reproduction of derived conclusions.

Genome-wide analysis of mitochondrial DNA copy number reveals loci implicated in nucleotide metabolism, platelet activation, and megakaryocyte proliferation - R. J. Longchamps; S. Y. Yang; C. A. Castellani; W. Shi; J. Lane; M. L. Grove; T. M. Bartz; C. Sarnowski; C. Liu; K. Burrows; A. L. Guyatt; T. R. Gaunt; et al. (Human Genetics, 2022)
Mitochondrial DNA copy number (mtDNA-CN) measured from blood specimens is a minimally invasive marker of mitochondrial function that exhibits both inter-individual and intercellular variation. To identify genes involved in regulating mitochondrial function, we performed a genome-wide association study (GWAS) in 465,809 White individuals from the Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) consortium and the UK Biobank (UKB). We identified 133 SNPs with statistically significant, independent effects associated with mtDNA-CN across 100 loci. A combination of fine-mapping, variant annotation, and co-localization analyses was used to prioritize genes within each of the 133 independent sites. Putative causal genes were enriched for known mitochondrial DNA depletion syndromes ( p = 3.09 × 10 –15 ) and the gene ontology (GO) terms for mtDNA metabolism ( p = 1.43 × 10 –8 ) and mtDNA replication ( p = 1.2 × 10 –7 ). A clustering approach leveraged pleiotropy between mtDNA-CN associated SNPs and 41 mtDNA-CN associated phenotypes to identify functional domains, revealing three distinct groups, including platelet activation, megakaryocyte proliferation, and mtDNA metabolism. Finally, using mitochondrial SNPs, we establish causal relationships between mitochondrial function and a variety of blood cell-related traits, kidney function, liver function and overall ( p = 0.044) and non-cancer mortality ( p = 6.56 × 10 –4 ).

Testing a global standard for quantifying species recovery and assessing conservation impact - Molly K. Grace; H. Resit Akçakaya; Elizabeth L. Bennett; Thomas M. Brooks; Anna Heath; Simon Hedges; Craig Hilton‐Taylor; Michael Hoffmann; Axel Hochkirch; Richard Jenkins; David A. Keith; Barney Long; et al. (Conservation Biology, 2021)
Recognizing the imperative to evaluate species recovery and conservation impact, in 2012 the International Union for Conservation of Nature (IUCN) called for development of a “Green List of Species” (now the IUCN Green Status of Species). A draft Green Status framework for assessing species’ progress toward recovery, published in 2018, proposed 2 separate but interlinked components: a standardized method (i.e., measurement against benchmarks of species’ viability, functionality, and preimpact distribution) to determine current species recovery status (herein species recovery score ) and application of that method to estimate past and potential future impacts of conservation based on 4 metrics ( conservation legacy, conservation dependence , conservation gain , and recovery potential ). We tested the framework with 181 species representing diverse taxa, life histories, biomes, and IUCN Red List categories (extinction risk). Based on the observed distribution of species’ recovery scores, we propose the following species recovery categories : fully recovered, slightly depleted, moderately depleted, largely depleted, critically depleted, extinct in the wild, and indeterminate. Fifty‐nine percent of tested species were considered largely or critically depleted. Although there was a negative relationship between extinction risk and species recovery score, variation was considerable. Some species in lower risk categories were assessed as farther from recovery than those at higher risk. This emphasizes that species recovery is conceptually different from extinction risk and reinforces the utility of the IUCN Green Status of Species to more fully understand species conservation status. Although extinction risk did not predict conservation legacy, conservation dependence, or conservation gain, it was positively correlated with recovery potential. Only 1.7% of tested species were categorized as zero across all 4 of these conservation impact metrics , indicating that conservation has, or will, play a role in improving or maintaining species status for the vast majority of these species. Based on our results, we devised an updated assessment framework that introduces the option of using a dynamic baseline to assess future impacts of conservation over the short term to avoid misleading results which were generated in a small number of cases, and redefines short term as 10 years to better align with conservation planning. These changes are reflected in the IUCN Green Status of Species Standard.

Use of pooled serum samples to assess herd disease status using commercially available ELISAs - Juan Heberth Hernandez-Medrano; Luis Fernando Espinosa-Castillo; Ana D. Rodriguez; Carlos G. Gutierrez; Wendela Wapenaar (Tropical Animal Health and Production, 2021)
Pooled samples are used in veterinary and human medicine as a cost-effective approach to monitor disease prevalence. Nonetheless, there is limited information on the effect of pooling on test performance, and research is required to determine the appropriate number of samples which can be pooled. Therefore, this study aimed to evaluate the use of pooled serum samples as a herd-level surveillance tool for infectious production-limiting diseases: bovine viral diarrhoea (BVD), infectious bovine rhinotracheitis (IBR), enzootic bovine leukosis (EBL) and Neospora caninum (NC), by investigating the maximum number of samples one can pool to identify one positive animal, using commercial antibody-detection ELISAs. Four positive field standards (PFS), one for each disease, were prepared by pooling highly positive herd-level samples diagnosed using commercially available ELISA tests. These PFS were used to simulate 18 pooled samples ranging from undiluted PFS to a dilution representing 1 positive in 1,000 animals using phosphate-buffered saline as diluent. A 1:10 dilution of the PFS resulted in positive results for IBR, BVD and EBL. Moreover, for IBR and BVD, results were still positive at 1:100 and 1:30 dilutions, respectively. However, for NC, a lower dilution (8:10) was required for a seropositive result. This study indicates that, at herd-level, the use of pooled serum is a useful strategy for monitoring infectious diseases (BVD, IBR and EBL) but not NC, using readily available diagnostic assays.

Pterocarpus marsupium extract extends replicative lifespan in budding yeast - Mitchell B. Lee; Michael G. Kiflezghi; Mitsuhiro Tsuchiya; Brian Wasko; Daniel T. Carr; Priya A. Uppal; Katherine A. Grayden; Yordanos C. Elala; Tu Anh Nguyen; Jesse Wang; Priya Ragosti; Sunny Nguyen; et al. (GeroScience, 2021)

Correction to: Bacterial etiology of community-acquired pneumonia in immunocompetent hospitalized patients and appropriateness of empirical treatment recommendations: an international point-prevalence study - Manuela Carugati; S. Aliberti; G. Sotgiu; F. Blasi; A. Gori; R. Menendez; M. Encheva; M. Gallego; P. Leuschner; S. Ruiz-Buitrago; S. Battaglia; R. Fantini; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Molecular systematics of the Awaous banana complex (River gobies; Teleostei: Oxudercidae ) - Caleb D. McMahan; Diego J. Elías; Yue Li; Omár Domínguez‐Domínguez; Sheila Rodriguez‐Machado; Alejandra Morales‐Cabrera; Diana Velásquez‐Ramírez; Kyle R. Piller; Prosanta Chakrabarty; Wilfredo A. Matamoros (Journal of Fish Biology, 2021)
Diadromous fishes can exhibit interesting evolutionary and population‐level patterns given their use of freshwater and marine environments as part of their life histories. The River goby genus Awaous are prominent members of riverine ichthyofaunas and occur throughout Atlantic and Pacific slopes of the Americas from the southern United States to Ecuador and Brazil. Here we study the widespread and polymorphic Awaous banana complex to assess phylogeographic patterns and test previous hypotheses that all populations of this species in the Americas belong to the same species. Analysis of sequence data based on the mitochondrial cytochrome oxidase I gene shows multiple clades within the Atlantic and Pacific basins, which correspond to previously described species. Additionally, haplotype analysis demonstrates unique and unconnected networks between these species. Within these clades we document biogeographic patterns that are congruent with results of other co‐occurring diadromous species, as well as a novel biogeographic pattern for the region. Our results support the recognition of distinct species of Awaous in the Atlantic ( A. banana and A. tajasica ) and Pacific ( A. transandeanus ) basins. These results are concordant with previously established morphological characters permitting the separation of these species.

Nutritional and ecotoxicological aspects of the acidotolerant alga Keratococcus rhaphidioides (Chlorophyta): a potential candidate for algal mediated bioremediation of extremely acidic waters - J. M. Cabrera; S. S. Schultz; G. D. Baffico; M. C. Rodriguez; F. L. Pedrozo; M. M. Diaz (Journal of Applied Phycology, 2021)

Around the world in 10 million years: Rapid dispersal of a kleptoparasitoid spider wasp (Pompilidae: Ceropales ) - Juanita Rodriguez; Sarah Bank; Cecilia Waichert; Carol D. von Dohlen; James P. Pitts (Journal of Biogeography, 2021)
Aim Cosmopolitan distributions have classically been explained by Pangaean vicariance. However, evidence of recently diverged cosmopolitan groups has re‐opened consideration on the processes involved. Our aim is to estimate the processes leading to the worldwide distribution of the kleptoparasitoid genus Ceropales . Location Worldwide. Taxon Ceropales spider wasps (Pompilidae). Methods Data from three molecular markers for 52 specimens of Ceropales and two calibration points from previous analyses were used to reconstruct a dated phylogeny under a relaxed molecular clock. We compared the fit of 12 models using BioGeoBEARS: DEC (subset sympatry, narrow vicariance), DIVALIKE (narrow and wide vicariance), BAYAREALIKE (widespread sympatry), and these same models with an added jump dispersal parameter and constraining dispersal rates among areas. Using the AIC best‐fit model (DEC+J), we performed Biogeographic Stochastic Mapping (BSM) to infer biogeographic processes by simulating 200 BSM on the BEAST chronogram. Results The origin of crown‐group Ceropales was ca. 10.6 Ma (15.7–6.5 95% HPD), and 11 jump‐dispersal events explain its distribution. A constrained DEC+J model, allowing adjacent area dispersal was the best‐fit AIC model. Dispersals across the Bering land bridge, Isthmus of Panama, Mediterranean Sea, and Sunda Plains took place from the late Miocene to present times. Main conclusions Ceropales is a recently diverged group that originated in Eurasia in the Miocene and dispersed to occupy the Americas, Africa, and Australia. Colonization was probably favored by the already diversified hosts (Pompilinae and Pepsinae), which reduced limiting factors such as food resource and nest construction. The evolution of a generalist parasitic lifestyle could facilitate long‐distance dispersal. This is the first study addressing the global historical biogeography of a cosmopolitan spider wasp.

Gene Expression Response to Stony Coral Tissue Loss Disease Transmission in M. cavernosa and O. faveolata From Florida - Nikki Traylor-Knowles; Michael T. Connelly; Benjamin D. Young; Katherine Eaton; Erinn M. Muller; Valerie J. Paul; Blake Ushijima; Allyson DeMerlis; Melissa K. Drown; Ashley Goncalves; Nicholas Kron; Grace A. Snyder; et al. (Frontiers in Marine Science, 2021)
Since 2014, corals within Florida’s Coral Reef have been dying at an unprecedented rate due to stony coral tissue loss disease (SCTLD). Here we describe the transcriptomic outcomes of three different SCTLD transmission experiments performed at the Smithsonian Marine Station and Mote Marine Laboratory between 2019 and 2020 on the corals Orbicella faveolata and Montastraea cavernosa. Overall, diseased O. faveolata had 2194 differentially expressed genes (DEGs) compared with healthy colonies, whereas diseased M. cavernosa had 582 DEGs compared with healthy colonies. Many significant DEGs were implicated in immunity, extracellular matrix rearrangement, and apoptosis. These included, but not limited to, peroxidases, collagens, Bax-like, fibrinogen-like, protein tyrosine kinase, and transforming growth factor beta. A gene module was identified that was significantly correlated to disease transmission. This module possessed many apoptosis and immune genes with high module membership indicating that a complex apoptosis and immune response is occurring in corals during SCTLD transmission. Overall, we found that O. faveolata and M. cavernosa exhibit an immune, apoptosis, and tissue rearrangement response to SCTLD. We propose that future studies should focus on examining early time points of infection, before the presence of lesions, to understand the activating mechanisms involved in SCTLD.

A robust machine learning framework to identify signatures for frailty: a nested case-control study in four aging European cohorts - David Gomez-Cabrero; Stefan Walter; Imad Abugessaisa; Rebeca Miñambres-Herraiz; Lucia Bernad Palomares; Lee Butcher; Jorge D. Erusalimsky; Francisco Jose Garcia-Garcia; José Carnicero; Timothy C. Hardman; Harald Mischak; Petra Zürbig; et al. (GeroScience, 2021)

Recombinant C-Terminal Domains from Scorpine-like Peptides Inhibit the Plasmodium berghei Ookinete Development In Vitro - Leonel Vargas-Jaimes; María Carmen Rodriguez; Rocío Argotte-Ramos; Víctor Rivelino Juárez-González; Nina Pastor; Catherine Cesa-Luna; Lourival D. Possani; Verónica Quintero-Hernández (International Journal of Peptide Research and Therapeutics, 2021)

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

Ageusia and anosmia, a common sign of COVID-19? A case series from four countries - Jair Vargas-Gandica; Daniel Winter; Rainer Schnippe; Andrea G. Rodriguez-Morales; Johana Mondragon; Juan Pablo Escalera-Antezana; María del Pilar Trelles-Thorne; D. Katterine Bonilla-Aldana; Alfonso J. Rodriguez-Morales; Alberto Paniz-Mondolfi (Journal of NeuroVirology, 2020)

The global abundance of tree palms - Robert Muscarella; Thaise Emilio; Oliver L. Phillips; Simon L. Lewis; Ferry Slik; William J. Baker; Thomas L. P. Couvreur; Wolf L. Eiserhardt; Jens‐Christian Svenning; Kofi Affum‐Baffoe; Shin‐Ichiro Aiba; Everton C. de Almeida; et al. (Global Ecology and Biogeography, 2020)
Aim Palms are an iconic, diverse and often abundant component of tropical ecosystems that provide many ecosystem services. Being monocots, tree palms are evolutionarily, morphologically and physiologically distinct from other trees, and these differences have important consequences for ecosystem services (e.g., carbon sequestration and storage) and in terms of responses to climate change. We quantified global patterns of tree palm relative abundance to help improve understanding of tropical forests and reduce uncertainty about these ecosystems under climate change. Location Tropical and subtropical moist forests. Time period Current. Major taxa studied Palms (Arecaceae). Methods We assembled a pantropical dataset of 2,548 forest plots (covering 1,191 ha) and quantified tree palm (i.e., ≥10 cm diameter at breast height) abundance relative to co‐occurring non‐palm trees. We compared the relative abundance of tree palms across biogeographical realms and tested for associations with palaeoclimate stability, current climate, edaphic conditions and metrics of forest structure. Results On average, the relative abundance of tree palms was more than five times larger between Neotropical locations and other biogeographical realms. Tree palms were absent in most locations outside the Neotropics but present in >80% of Neotropical locations. The relative abundance of tree palms was more strongly associated with local conditions (e.g., higher mean annual precipitation, lower soil fertility, shallower water table and lower plot mean wood density) than metrics of long‐term climate stability. Life‐form diversity also influenced the patterns; palm assemblages outside the Neotropics comprise many non‐tree (e.g., climbing) palms. Finally, we show that tree palms can influence estimates of above‐ground biomass, but the magnitude and direction of the effect require additional work. Conclusions Tree palms are not only quintessentially tropical, but they are also overwhelmingly Neotropical. Future work to understand the contributions of tree palms to biomass estimates and carbon cycling will be particularly crucial in Neotropical forests.

Compound-specific δ2H analysis highlights the relationship between direct assimilation and de novo synthesis of amino acids from food and water in a terrestrial mammalian omnivore - Seth D. Newsome; Bobby J. Nakamoto; Mauriel Rodriguez Curras; Marilyn L. Fogel (Oecologia, 2020)

Bacterial etiology of community-acquired pneumonia in immunocompetent hospitalized patients and appropriateness of empirical treatment recommendations: an international point-prevalence study - Manuela Carugati; S. Aliberti; G. Sotgiu; F. Blasi; A. Gori; R. Menendez; M. Encheva; M. Gallego; P. Leuschner; S. Ruiz-Buitrago; S. Battaglia; R. Fantini; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

A Cautionary Tale: Quantitative LC-HRMS Analytical Procedures for the Analysis of N-Nitrosodimethylamine in Metformin - Jingyue Yang; Tim Andres Marzan; Wei Ye; Cynthia D. Sommers; Jason D. Rodriguez; David A. Keire (The AAPS Journal, 2020)
A private testing laboratory reported in a Citizen Petition (CP) to FDA that 16 of 38 metformin drug products they tested had N -nitrosodimethyl amine (NDMA) amounts above the allowable intake (AI) of 96 ng/day. Because the FDA had been monitoring drugs for nitrosamines, orthogonal analytical procedures had been developed, validated and applied to detect the following nitrosamines in metformin drug products (if present): (i) NDMA (with a dedicated method) or (ii) NDMA (with a second confirmatory method), N -nitroso-diethylamine (NDEA), N -ethyl- N -nitroso-2-propanamine (NEIPA), N -nitroso-diisopropylamine (NDIPA), N -nitroso-di-n-propylamine (NDPA), N -nitroso-methylphenylamine (NMPA), N -nitroso-di-n-butylamine (NDBA) and N -nitroso- N -methyl-4-aminobutyric acid (NMBA). In contrast to the private laboratory results, FDA testing on the same set of 38 samples with orthogonal procedures observed amounts over the AI in only 8 of the 38 products and generally observed lower values than reported by the private testing laboratory. As described here, the investigation into the cause of the discrepancy revealed that N,N -dimethylformamide (DMF) can interfere with NDMA measurements. The data showed that the use of sufficient mass accuracy in the data acquisition and appropriate mass tolerance setting in the data processing to assure the selectivity of mass spectrometry measurements of NDMA in the presence of co-eluting DMF was necessary to prevent overestimation of the level of NDMA in metformin drug products. Overall, care should be taken to assure the necessary specificity in analytical procedures for adequate assessment of the nitrosamine level in drug products that also contain DMF or other potential interfering substances.

An NMR Protocol for In Vitro Paclitaxel Release from an Albumin-Bound Nanoparticle Formulation - Min Sung Suh; Sharadrao M. Patil; Darby Kozak; Eric Pang; Stephanie Choi; Xiaohui Jiang; Jason D. Rodriguez; David A. Keire; Kang Chen (AAPS PharmSciTech, 2020)

Diabetes and cardiovascular disease mortality among a population-based cohort of women with and without breast cancer - Luis A. Rodriguez; Patrick T. Bradshaw; Humberto Parada; Nikhil K. Khankari; Tengteng Wang; Rebecca J. Cleveland; Susan L. Teitelbaum; Alfred I. Neugut; Marilie D. Gammon (Cancer Causes & Control, 2020)

Adenovirus-Mediated Transduction of Insulin-Like Growth Factor 1 Protects Hippocampal Neurons from the Toxicity of Aβ Oligomers and Prevents Memory Loss in an Alzheimer Mouse Model - Maria Clara Selles; Juliana T. S. Fortuna; Maria F. Zappa-Villar; Yasmin P. R. de Faria; Amanda S. Souza; Claudia K. Suemoto; Renata E. P. Leite; Roberta D. Rodriguez; Lea T. Grinberg; Paula C. Reggiani; Sergio T. Ferreira (Molecular Neurobiology, 2020)

A comparison of regional brain volumes and white matter connectivity in subjects with stimulant induced psychosis versus schizophrenia - Peter D. Alexander; Kristina M. Gicas; Alex Cheng; Donna J. Lang; Ric M. Procyshyn; Alexandra T. Vertinsky; William J. Panenka; Allen E. Thornton; Alexander Rauscher; Jamie Y. X. Wong; Tasha Chan; Andrea A. Jones; et al. (Psychopharmacology, 2019)

Mechanistic Insights into Factor VIII Immune Tolerance Induction via Prenatal Cell Therapy in Hemophilia A - Martin Rodriguez; Christopher D. Porada; Graça Almeida-Porada (Current Stem Cell Reports, 2019)

Essential in vitro diagnostics for advanced HIV and serious fungal diseases: international experts’ consensus recommendations - Felix Bongomin; Nelesh P. Govender; Arunaloke Chakrabarti; Florence Robert-Gangneux; David R. Boulware; Afia Zafar; Rita O. Oladele; Malcolm D. Richardson; Jean-Pierre Gangneux; Ana Alastruey-Izquierdo; Joel Bazira; Tom H. Boyles; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2019)

Integrated Observations of Global Surface Winds, Currents, and Waves: Requirements and Challenges for the Next Decade - Ana B. Villas Bôas; Fabrice Ardhuin; Alex Ayet; Mark A. Bourassa; Peter Brandt; Betrand Chapron; Bruce D. Cornuelle; J. T. Farrar; Melanie R. Fewings; Baylor Fox-Kemper; Sarah T. Gille; Christine Gommenginger; et al. (Frontiers in Marine Science, 2019)

Cross-Cultural Medical Care Training and Education: a National Survey of Pediatric Hematology/Oncology Fellows-in-Training and Fellowship Program Directors - Amulya A. Nageswara Rao; Deepti M. Warad; Amy L. Weaver; Cathy D. Schleck; Vilmarie Rodriguez (Journal of Cancer Education, 2019)

pH Variability Exacerbates Effects of Ocean Acidification on a Caribbean Crustose Coralline Alga - Maggie D. Johnson; Lucia M. Rodriguez Bravo; Shevonne E. O’Connor; Nicholas F. Varley; Andrew H. Altieri (Frontiers in Marine Science, 2019)

Contributions of Hydrology to Vesicular Stomatitis Virus Emergence in the Western USA - Emile Elias; D. Scott McVey; Debra Peters; Justin D. Derner; Angela Pelzel-McCluskey; T. Scott Schrader; Luis Rodriguez (Ecosystems, 2019)

Adenovirus 5 produces obesity and adverse metabolic, morphological, and functional changes in the long term in animals fed a balanced diet or a high-fat diet: a study on hamsters - Daniel A. Montes-Galindo; Ana C. Espiritu-Mojarro; Valery Melnikov; Norma A. Moy-López; Alejandro D. Soriano-Hernandez; Hector R. Galvan-Salazar; Jorge Guzman-Muñiz; Jose Guzman-Esquivel; Margarita L. Martinez-Fierro; Iram P. Rodriguez-Sanchez; Brenda Paz-Michel; Sergio A. Zaizar-Fregoso; et al. (Archives of Virology, 2019)

Climate Change and Atlantic Multidecadal Oscillation as Drivers of Recent Declines in Coral Growth Rates in the Southwestern Caribbean - Luis D. Lizcano-Sandoval; Ángela Marulanda-Gómez; Mateo López-Victoria; Alberto Rodriguez-Ramirez (Frontiers in Marine Science, 2019)

An Expandable Mechanopharmaceutical Device (1): Measuring the Cargo Capacity of Macrophages in a Living Organism - Phillip Rzeczycki; Tehetina Woldemichael; Andrew Willmer; Mikhail D. Murashov; Jason Baik; Rahul Keswani; Gi Sang Yoon; Kathleen A. Stringer; Nair Rodriguez-Hornedo; Gus R. Rosania (Pharmaceutical Research, 2019)

The voltage-sensitive cardiac M2 muscarinic receptor modulates the inward rectification of the G protein-coupled, ACh-gated K+ current - Pedro D. Salazar-Fajardo; Iván A. Aréchiga-Figueroa; Ana Laura López-Serrano; Julio C. Rodriguez-Elias; Javier Alamilla; José A. Sánchez-Chapula; Martin Tristani-Firouzi; Ricardo A. Navarro-Polanco; Eloy G. Moreno-Galindo (Pflügers Archiv - European Journal of Physiology, 2018)

Inhibitory activity of methanol extracts from different colored flowers on aldose reductase and HPLC-UV analysis of quercetin - Norman G. Quilantang; Seo Hyun Ryu; Se Hoon Park; Jae Sang Byun; Je Sung Chun; Ju Sung Lee; Joyce P. Rodriguez; Young-Seok Yun; Sonia D. Jacinto; Sanghyun Lee (Horticulture, Environment, and Biotechnology, 2018)

Intra-organismal variation in the structure of plant vascular transport tissues in poplar trees - Anna L. Jacobsen; Jessica Valdovinos-Ayala; F. Daniela Rodriguez-Zaccaro; M. Angela Hill-Crim; Marta I. Percolla; Martin D. Venturas (Trees, 2018)

Assimilation and discrimination of hydrogen isotopes in a terrestrial mammal - Mauriel Rodriguez Curras; Marilyn L. Fogel; Seth D. Newsome (Oecologia, 2018)

Invasive pulmonary aspergillosis is associated with adverse clinical outcomes in critically ill patients receiving veno-venous extracorporeal membrane oxygenation - I. Rodriguez-Goncer; S. Thomas; P. Foden; M. D. Richardson; A. Ashworth; J. Barker; C. G. Geraghty; E. G. Muldoon; T. W. Felton (European Journal of Clinical Microbiology & Infectious Diseases, 2018)

Transcriptomic changes in Echinochloa colona in response to treatment with the herbicide imazamox - Alice A. Wright; Rajkumar Sasidharan; Liisa Koski; Marianela Rodriguez-Carres; Daniel G. Peterson; Vijay K. Nandula; Jeffery D. Ray; Jason A. Bond; David R. Shaw (Planta, 2018)

Determination of flavonoids in Acer okamotoanum and their aldose reductase inhibitory activities - Jaemin Lee; Dong-Gu Lee; Joyce P. Rodriguez; Jun Yeon Park; Eun Ju Cho; Sonia D. Jacinto; Sanghyun Lee (Horticulture, Environment, and Biotechnology, 2018)

Adapting clonally propagated crops to climatic changes: a global approach for taro (Colocasia esculenta (L.) Schott) - V. Lebot; V. Tuia; A. Ivancic; G. V. H. Jackson; F. Saborio; G. Reyes; S. Rodriguez; G. Robin; R. Traoré; L. Aboagye; J. Onyeka; W. van Rensburg; et al. (Genetic Resources and Crop Evolution, 2018)

Anaerobic microplate assay for direct microbial conversion of switchgrass and Avicel using Clostridium thermocellum - Gbekeloluwa B. Oguntimein; Miguel Rodriguez; Alexandru Dumitrache; Todd Shollenberger; Stephen R. Decker; Brian H. Davison; Steven D. Brown (Biotechnology Letters, 2018)

Fast versus slow growing tuna species: age, growth, and implications for population dynamics and fisheries management - Hilario Murua; Enrique Rodriguez-Marin; John D. Neilson; Jessica H. Farley; María Jose Juan-Jordá (Reviews in Fish Biology and Fisheries, 2017)

An intravaginal ring that releases three antiviral agents and a contraceptive blocks SHIV-RT infection, reduces HSV-2 shedding, and suppresses hormonal cycling in rhesus macaques - Nina Derby; Meropi Aravantinou; Jessica Kenney; Shweta R. Ugaonkar; Asa Wesenberg; Jolanta Wilk; Larisa Kizima; Aixa Rodriguez; Shimin Zhang; Olga Mizenina; Keith Levendosky; Michael L. Cooney; et al. (Drug Delivery and Translational Research, 2017)

Ventilator-associated pneumonia by methicillin-susceptible Staphylococcus aureus: do minimum inhibitory concentrations to vancomycin and daptomycin matter? - J. Ruiz-Ramos; P. Vidal-Cortés; A. Díaz-Lamas; R. Reig-Valero; F. Roche-Campo; M. Del Valle-Ortiz; X. Nuvials-Casals; M. Ortiz-Piquer; D. Andaluz-Ojeda; L. Tamayo-Lomas; M. A. Blasco-Navalpotro; M. Rodriguez-Aguirregabiria; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2017)

Mathematical Modeling of Normal and Cancer Stem Cells - Lora D. Weiss; Natalia L. Komarova; Ignacio A. Rodriguez-Brenes (Current Stem Cell Reports, 2017)

A comparison of psychotic symptoms in subjects with methamphetamine versus cocaine dependence - Peter D Alexander; Kristina M Gicas; Taylor S Willi; Clara N Kim; Veronika Boyeva; Ric M Procyshyn; Geoff N. Smith; Allen E Thornton; William J Panenka; Andrea A. Jones; Fidel Vila-Rodriguez; Donna J. Lang; et al. (Psychopharmacology, 2017)

Spatio-temporal monitoring by ground-based and air- and space-borne lidars of a moderate Saharan dust event affecting southern Europe in June 2013 in the framework of the ADRIMED/ChArMEx campaign - R. Barragan; M. Sicard; J. Totems; J. F. Léon; F. Dulac; M. Mallet; J. Pelon; L. Alados-Arboledas; A. Amodeo; P. Augustin; A. Boselli; J. A. Bravo-Aranda; et al. (Air Quality, Atmosphere & Health, 2017)

The influence of slope-angle ratio on the dynamics of granular flows: insights from laboratory experiments - R. Sulpizio; D. Castioni; L. A. Rodriguez-Sedano; D. Sarocchi; F. Lucchi (Bulletin of Volcanology, 2016)

Engaging diverse populations in biospecimen donation: results from the Hoy y Mañana study - Elisa M. Rodriguez; Frances G. Saad-Harfouche; Austin Miller; Martin C. Mahoney; Christine B. Ambrosone; Carl D. Morrison; Willie Underwood; Deborah O. Erwin (Journal of Community Genetics, 2016)

Effectiveness of sequential intravenous-to-oral antibiotic switch therapy in hospitalized patients with gram-positive infection: the SEQUENCE cohort study - D. Rodriguez-Pardo; C. Pigrau; D. Campany; V. Diaz-Brito; L. Morata; I. C. de Diego; L. Sorlí; S. Iftimie; R. Pérez-Vidal; G. García-Pardo; T. Larrainzar-Coghen; B. Almirante (European Journal of Clinical Microbiology & Infectious Diseases, 2016)

Soil mercury levels in the area surrounding the Cerro Prieto geothermal complex, MEXICO - M. A. Pastrana-Corral; F. T. Wakida; E. García-Flores; D. D. Rodriguez-Mendivil; A. Quiñonez-Plaza; T. D. J. Piñon-Colin (Environmental Monitoring and Assessment, 2016)

Amphibian‐killing chytrid in B razil comprises both locally endemic and globally expanding populations - T. S. Jenkinson; C. M. Betancourt Román; C. Lambertini; A. Valencia‐Aguilar; D. Rodriguez; C. H. L. Nunes‐de‐Almeida; J. Ruggeri; A. M. Belasen; D. da Silva Leite; K. R. Zamudio; J. E. Longcore; L. F. Toledo; et al. (Molecular Ecology, 2016)
Chytridiomycosis, caused by the fungus Batrachochytrium dendrobatidis ( Bd ), is the emerging infectious disease implicated in recent population declines and extinctions of amphibian species worldwide. Bd strains from regions of disease‐associated amphibian decline to date have all belonged to a single, hypervirulent clonal genotype ( Bd ‐ GPL ). However, earlier studies in the Atlantic Forest of southeastern Brazil detected a novel, putatively enzootic lineage ( Bd ‐Brazil), and indicated hybridization between Bd ‐ GPL and Bd ‐Brazil. Here, we characterize the spatial distribution and population history of these sympatric lineages in the Brazilian Atlantic Forest. To investigate the genetic structure of Bd in this region, we collected and genotyped Bd strains along a 2400‐km transect of the Atlantic Forest. Bd ‐Brazil genotypes were restricted to a narrow geographic range in the southern Atlantic Forest, while Bd ‐ GPL strains were widespread and largely geographically unstructured. Bd population genetics in this region support the hypothesis that the recently discovered Brazilian lineage is enzootic in the Atlantic Forest of Brazil and that Bd ‐ GPL is a more recently expanded invasive. We collected additional hybrid isolates that demonstrate the recurrence of hybridization between panzootic and enzootic lineages, thereby confirming the existence of a hybrid zone in the Serra da Graciosa mountain range of Paraná State. Our field observations suggest that Bd ‐ GPL may be more infective towards native Brazilian amphibians, and potentially more effective at dispersing across a fragmented landscape. We also provide further evidence of pathogen translocations mediated by the Brazilian ranaculture industry with implications for regulations and policies on global amphibian trade.

Sulfide-oxidizing bacteria establishment in an innovative microaerobic reactor with an internal silicone membrane for sulfur recovery from wastewater - F. Valdés; P. R. Camiloti; R. P. Rodriguez; T. P. Delforno; J. Carrillo-Reyes; M. Zaiat; D. Jeison (Biodegradation, 2016)

Loss and gains in ant–plant interactions mediated by extrafloral nectar: fidelity, cheats, and lies - K. Del-Claro; V. Rico-Gray; H. M. Torezan-Silingardi; E. Alves-Silva; R. Fagundes; D. Lange; W. Dáttilo; A. A. Vilela; A. Aguirre; D. Rodriguez-Morales (Insectes Sociaux, 2016)

Microcystin-tolerant Rhizobium protects plants and improves nitrogen assimilation in Vicia faba irrigated with microcystin-containing waters - Majida Lahrouni; Khalid Oufdou; Fatima El Khalloufi; Loubna Benidire; Susann Albert; Michael Göttfert; Miguel A. Caviedes; Ignacio D. Rodriguez-Llorente; Brahim Oudra; Eloísa Pajuelo (Environmental Science and Pollution Research, 2016)

Assessing the State of Contamination in a Historic Mining Town Using Sediment Chemistry - Mélida Gutiérrez; Shuo-Sheng Wu; Jameelah R. Rodriguez; Ashton D. Jones; Benjamin E. Lockwood (Archives of Environmental Contamination and Toxicology, 2016)

Storm water retention and actual evapotranspiration performances of experimental green roofs in French oceanic climate - D. Yilmaz; M. Sabre; L. Lassabatère; M. Dal; F. Rodriguez (European Journal of Environmental and Civil Engineering, 2016)

Estimated Per Capita Water Usage Associated with Different Levels of Water Scarcity Risk in Arid and Semiarid Regions - R. D. G. Rodriguez; F. F. Pruski; V. P. Singh (Water Resources Management, 2016)

First recurrence of Clostridium difficile infection: clinical relevance, risk factors, and prognosis - T. Larrainzar-Coghen; D. Rodriguez-Pardo; M. Puig-Asensio; V. Rodríguez; C. Ferrer; R. Bartolomé; C. Pigrau; N. Fernández-Hidalgo; T. Pumarola; B. Almirante (European Journal of Clinical Microbiology & Infectious Diseases, 2016)

Trends in early-stage hepatocellular carcinoma, California 1988–2010 - Danielle N. Rodriguez; Cara Torruellas; Rosemary D. Cress (Cancer Causes & Control, 2016)

Assessing stakeholder impacts and adaptation to low water-levels: the Trent-Severn waterway - J. M. A. Coleman; F. S. Sosa-Rodriguez; L. D. Mortsch; P. J. Deadman (Climatic Change, 2016)

Analysis of In Vitro Aptamer Selection Parameters - Maureen McKeague; Erin M. McConnell; Jose Cruz-Toledo; Elyse D. Bernard; Amanda Pach; Emily Mastronardi; Xueru Zhang; Michael Beking; Tariq Francis; Amanda Giamberardino; Ashley Cabecinha; Annamaria Ruscito; et al. (Journal of Molecular Evolution, 2015)

Differential gene transcription, biochemical responses, and cytotoxicity assessment in Pacific oyster Crassostrea gigas exposed to ibuprofen - Miguel A. S. Serrano; Maria Gonzalez-Rey; Jacó J. Mattos; Fabrício Flores-Nunes; Álvaro C. P. Mello; Flávia L. Zacchi; Clei E. Piazza; Marília N. Siebert; Rômi S. Piazza; Diana Alvarez-Muñoz; Sara Rodriguez-Mozaz; Damià Barceló; et al. (Environmental Science and Pollution Research, 2015)

Molecular evolution and in vitro characterization of Botryllus histocompatibility factor - Daryl A. Taketa; Marie L. Nydam; Adam D. Langenbacher; Delany Rodriguez; Erin Sanders; Anthony W. De Tomaso (Immunogenetics, 2015)

Cellular metabolism of unnatural sialic acid precursors - Nam D. Pham; Charles S. Fermaintt; Andrea C. Rodriguez; Janet E. McCombs; Nicole Nischan; Jennifer J. Kohler (Glycoconjugate Journal, 2015)

Fermentation of Dilute Acid Pretreated Populus by Clostridium thermocellum, Caldicellulosiruptor bescii, and Caldicellulosiruptor obsidiansis - Kelsey L. Yee; Miguel Rodriguez; Choo Y. Hamilton; Scott D. Hamilton-Brehm; Olivia A. Thompson; James G. Elkins; Brian H. Davison; Jonathan R. Mielenz (BioEnergy Research, 2015)

Linking coastal aquaculture of meagre Argyrosomus regius and Western Mediterranean coastal fisheries through escapes incidents - P. Arechavala‐Lopez; J. M. Valero‐Rodriguez; J. Peñalver‐García; D. Izquierdo‐Gomez; P. Sanchez‐Jerez (Fisheries Management and Ecology, 2015)
Escape incidents in coastal aquaculture lead to economic losses for farmers and may have indirect socio‐economic effects on local fisheries. In this study, the relationship of meagre, Argyrosomus regius (Asso), production in open‐sea cages and coastal small‐scale fisheries was analysed through captures of escapes, which are easily detected because this species is considered locally absent in native communities in Western Mediterranean regions. Scale reading showed that 100% of captured meagre were escapees. The existence of a direct relationship, in terms of biomass, between the development of meagre coastal aquaculture and the increase of captures of this species by local fisheries was demonstrated. The spatial distribution of meagre captures suggested that there is a local environmental and economic interaction between meagre aquaculture and fisheries through escapees. Monitoring the presence of locally absent species such as meagre within landings might help to assess the magnitude of escapes, the potential economic effects on local aquaculture and fishery industries, and the potential adverse ecological impacts on local ecosystems.

A hydrologic tracer study in a small, natural wetland in the humid tropics of Costa Rica - D. Kaplan; M. Bachelin; C. Yu; R. Muñoz-Carpena; Thomas L. Potter; W. Rodriguez-Chacón (Wetlands Ecology and Management, 2015)

Is Streptococcus bovis a urinary pathogen? - M. Matesanz; D. Rubal; I. Iñiguez; R. Rabuñal; F. García-Garrote; A. Coira; M. J. García-País; J. Pita; A. Rodriguez-Macias; M. J. López-Álvarez; M. P. Alonso; J. Corredoira (European Journal of Clinical Microbiology & Infectious Diseases, 2015)

Impacts of future climatic and land cover changes on the hydrological regime of the Madeira River basin - J. L. Siqueira Júnior; J. Tomasella; D. A. Rodriguez (Climatic Change, 2015)

Historical biogeography of the widespread spider wasp tribe Aporini (Hymenoptera: Pompilidae) - Juanita Rodriguez; James P. Pitts; Carol D. von Dohlen (Journal of Biogeography, 2015)
Aim Our aim was to determine the age and area of origin of the genera of the Aporini tribe of spider wasps by studying its historical biogeography. We also tested the fit of several hypotheses concerning the processes underlying the widespread distribution of this group. Location The Holarctic and Neotropics. Methods A phylogeny of 44 Aporini taxa was produced through Bayesian inference using four nuclear molecular markers (elongation factor‐1 α F2 copy, long‐wavelength rhodopsin, wingless and the D2–D3 regions of the 28S ribosomal RNA ). A lognormal relaxed molecular clock, calibrated with ages from three fossils, was used to estimate lineage divergence times. Biogeographical processes were studied using three methods: statistical dispersal–vicariance analysis (S‐ DIVA ), dispersal–extinction cladogenesis ( DEC ) analysis and Bayesian binary Markov chain Monte Carlo ( BBM ) analysis. Results Our data suggest an origin for the most recent common ancestor of extant Aporini in the Nearctic region in the early Miocene, 22.6 Ma, with a confidence interval ( CI ) of 17.40–28.83 Ma. All genera originated in the Miocene, four in the Nearctic region. A constrained DEC analysis, where only dispersal to adjacent regions was allowed, produced the highest likelihood and was mostly congruent with the BBM results. Main conclusions Dispersal from the Nearctic region to the Palaearctic region probably occurred across the Bering land bridge in the early Miocene, 15–18 Ma ( CI = 11.14, 23.52), while three dispersal events to South America from Mesoamerica took place independently. These dispersals to South America occurred after 18 Ma through the Isthmus of Panama or across the Panama seaway. Three independent over‐water dispersal events to the Antilles occurred from Mesoamerica and the Nearctic for two Aporini genera. The patterns inferred within the biogeographical history of Aporini agree with several scenarios proposed for other unrelated taxa.

Antifungal isolates database of amphibian skin‐associated bacteria and function against emerging fungal pathogens - Douglas C. Woodhams; Ross A. Alford; Rachael E. Antwis; Holly Archer; Matthew H. Becker; Lisa K. Belden; Sara C. Bell; Molly Bletz; Joshua H. Daskin; Leyla R. Davis; Sandra V. Flechas; Antje Lauer; et al. (Ecology, 2015)
Microbial symbionts of vertebrate skin have an important function in defense of the host against pathogens. In particular, the emerging chytrid fungus Batrachochytrium dendrobatidis , causes widespread disease in amphibians but can be inhibited via secondary metabolites produced by many different skin‐associated bacteria. Similarly, the fungal pathogens of terrestrial salamander eggs Mariannaea elegans and Rhizomucor variabilis are also inhibited by a variety of skin‐associated bacteria. Indeed, probiotic therapy against fungal diseases is a recent approach in conservation medicine with growing experimental support. We present a comprehensive Antifungal Isolates Database of amphibian skin‐associated bacteria that have been cultured, isolated, and tested for antifungal properties. At the start, this database includes nearly 2000 cultured bacterial isolates from 37 amphibian host species across 18 studies on five continents: Africa, Oceania, Europe, and North and South America. As the research community gathers information on additional isolates, the database will be updated periodically. The resulting database can serve as a conservation tool for amphibians and other organisms, and provides empirical data for comparative and bioinformatic studies. The database consists of a FASTA file containing 16S rRNA gene sequences of the bacterial isolates, and a metadata file containing information on the host species, life‐stage, geographic region, and antifungal capacity and taxonomic identity of the isolate.

Understanding the Patient-Provider Communication Needs and Experiences of Latina and Non-Latina White Women Following an Abnormal Mammogram - Yamile Molina; Sarah D. Hohl; Linda K. Ko; Edgar A. Rodriguez; Beti Thompson; Shirley A. A. Beresford (Journal of Cancer Education, 2014)

Testing a ‘genes‐to‐ecosystems’ approach to understanding aquatic–terrestrial linkages - Gregory M. Crutsinger; Seth M. Rudman; Mariano A. Rodriguez‐Cabal; Athena D. McKown; Takuya Sato; Andrew M. MacDonald; Julian Heavyside; Armando Geraldes; Edmund M. Hart; Carri J. LeRoy; Rana W. El‐Sabaawi (Molecular Ecology, 2014)
A ‘genes‐to‐ecosystems’ approach has been proposed as a novel avenue for integrating the consequences of intraspecific genetic variation with the underlying genetic architecture of a species to shed light on the relationships among hierarchies of ecological organization (genes → individuals → communities → ecosystems). However, attempts to identify genes with major effect on the structure of communities and/or ecosystem processes have been limited and a comprehensive test of this approach has yet to emerge. Here, we present an interdisciplinary field study that integrated a common garden containing different genotypes of a dominant, riparian tree, Populus trichocarpa , and aquatic mesocosms to determine how intraspecific variation in leaf litter alters both terrestrial and aquatic communities and ecosystem functioning. Moreover, we incorporate data from extensive trait screening and genome‐wide association studies estimating the heritability and genes associated with litter characteristics. We found that tree genotypes varied considerably in the quality and production of leaf litter, which contributed to variation in phytoplankton abundances, as well as nutrient dynamics and light availability in aquatic mesocosms. These ‘after‐life’ effects of litter from different genotypes were comparable to the responses of terrestrial communities associated with the living foliage. We found that multiple litter traits corresponding with aquatic community and ecosystem responses differed in their heritability. Moreover, the underlying genetic architecture of these traits was complex, and many genes contributed only a small proportion to phenotypic variation. Our results provide further evidence that genetic variation is a key component of aquatic–terrestrial linkages, but challenge the ability to predict community or ecosystem responses based on the actions of one or a few genes.

Safety and Injury Characteristics of Youth Farmworkers in North Carolina: A Pilot Study - Thomas A. Arcury; Guadalupe Rodriguez; Gregory D. Kearney; Justin T. Arcury; Sara A. Quandt (Journal of Agromedicine, 2014)

Engaging diverse populations about biospecimen donation for cancer research - Julie H. T. Dang; Elisa M. Rodriguez; John S. Luque; Deborah O. Erwin; Cathy D. Meade; Moon S. Chen (Journal of Community Genetics, 2014)

New subgroup 16SrIII-Y phytoplasmas associated with false-blossom diseased cranberry (Vaccinium macrocarpon) plants and with known and potential insect vectors in New Jersey - I.-M. Lee; J. Polashock; K. D. Bottner-Parker; P. G. Bagadia; C. Rodriguez-Saona; Y. Zhao; R. E. Davis (European Journal of Plant Pathology, 2014)

Development of 14 microsatellite markers in the Queensland koala (Phascolarctos cinereus adustus) using next generation sequencing technology - Christina T. Ruiz-Rodriguez; Yasuko Ishida; Alex D. Greenwood; Alfred L. Roca (Conservation Genetics Resources, 2014)

Social network analysis resolves temporal dynamics of male dominance relationships - David Bierbach; Sophie Oster; Jonas Jourdan; Lenin Arias-Rodriguez; Jens Krause; Alexander D. M. Wilson; Martin Plath (Behavioral Ecology and Sociobiology, 2014)

Direct ageing of Thunnus thynnus from the eastern Atlantic Ocean and western Mediterranean Sea using dorsal fin spines - P. L. Luque; E. Rodriguez‐Marin; J. Landa; M. Ruiz; P. Quelle; D. Macias; J. M. Ortiz De Urbina (Journal of Fish Biology, 2014)
This study deals with important methodology issues that affect age estimates of eastern Atlantic bluefin tuna Thunnus thynnus using dorsal fin spines. Nearly 3800 spine sections were used from fish caught in the north‐east Atlantic Ocean and western Mediterranean Sea over a 21 year period. Edge type and marginal increment analyses indicated a yearly periodicity of annulus formation with the translucent bands (50% of occurrence) appearing from October to May. Nucleus vascularization seriously affected specimens older than 6 years, with the disappearance of 40–50% of the presumed annuli by that age. An alternate sectioning location was a clear improvement and this finding is an important contribution to the methodology of using this structure for ageing the full‐length range of eastern T. thynnus . Finally, there were no significant differences between the coefficients of von Bertalanffy growth model estimated from mean length at age data ( L ∞ = 327·4; k = 0·097; t 0 = −0·838) and those estimated from the growth curves accepted for the eastern and western T. thynnus management units.

Discrepant results from sampling different lumens of multilumen catheters: the case for sampling all lumens - J. Cuellar-Rodriguez; D. Connor; P. Murray; J. Gea-Banacloche (European Journal of Clinical Microbiology & Infectious Diseases, 2014)

Journal Clubs: An Educational Approach to Advance Understanding Among Community Partners and Academic Researchers About CBPR and Cancer Health Disparities - Susan T. Vadaparampil; Vani N. Simmons; Ji-Hyun Lee; Teri Malo; Lynne Klasko; Maria Rodriguez; Rhonda Waddell; Clement K. Gwede; Cathy D. Meade (Journal of Cancer Education, 2014)

High-quality conforming hexahedral meshes of patient-specific abdominal aortic aneurysms including their intraluminal thrombi - J. Tarjuelo-Gutierrez; B. Rodriguez-Vila; D. M. Pierce; T. E. Fastl; P. Verbrugghe; I. Fourneau; G. Maleux; P. Herijgers; G. A. Holzapfel; E. J. Gomez (Medical & Biological Engineering & Computing, 2014)

Long‐term endemism of two highly divergent lineages of the amphibian‐killing fungus in the A tlantic F orest of B razil - D. Rodriguez; C. G. Becker; N. C. Pupin; C. F. B. Haddad; K. R. Zamudio (Molecular Ecology, 2014)
The recent global spread of the amphibian‐killing fungus [ B atrachochytrium dendrobatidis ( Bd )] has been closely tied to anthropogenic activities; however, regional patterns of spread are not completely understood. Using historical samples, we can test whether B d was a spreading or endemic pathogen in a region within a particular time frame, because those two disease states provide different predictions for the regional demographic dynamics and population genetics of B d . Testing historical patterns of pathogen prevalence and population genetics under these predictions is key to understanding the evolution and origin of B d . Focusing on the A tlantic F orest ( AF ) of B razil, we used q PCR assays to determine the presence or absence of B d on 2799 preserved postmetamorphic anurans collected between 1894 and 2010 and used semi‐nested PCR s to determine the frequency of r RNA ITS 1 haplotypes from 52 samples. Our earliest date of detection was 1894. A mean prevalence of 23.9% over time and spatiotemporal patterns of B d clusters indicate that B d has been enzootic in the B razilian AF with no evidence of regional spread within the last 116 years. ITS 1 haplotypes confirm the long‐term presence of two divergent strains of B d ( B d GPL and B d‐Brazil ) and three spatiotemporally broad genetic demes within B d GPL , indicating that B d was not introduced into southeast B razil by the bullfrog trade. Our data show that the evolutionary history and pathogen dynamics of B d in B razil is better explained by the endemic pathogen hypothesis.

Diffusional conductances to CO2 as a target for increasing photosynthesis and photosynthetic water-use efficiency - Jaume Flexas; Ülo Niinemets; Alexander Gallé; Margaret M. Barbour; Mauro Centritto; Antonio Diaz-Espejo; Cyril Douthe; Jeroni Galmés; Miquel Ribas-Carbo; Pedro L. Rodriguez; Francesc Rosselló; Raju Soolanayakanahally; et al. (Photosynthesis Research, 2013)

Optimization of a Trap for Tuta absoluta Meyrick (Lepidoptera: Gelechiidae) and Trials to Determine the Effectiveness of Mass Trapping - E Lobos; M Occhionero; D Werenitzky; J Fernandez; L M Gonzalez; C Rodriguez; C Calvo; G Lopez; A C Oehlschlager (Neotropical Entomology, 2013)

Bivalve distribution in hydrographic regions in South America: historical overview and conservation - Daniel Pereira; Maria Cristina Dreher Mansur; Leandro D. S. Duarte; Arthur Schramm de Oliveira; Daniel Mansur Pimpão; Cláudia Tasso Callil; Cristián Ituarte; Esperanza Parada; Santiago Peredo; Gustavo Darrigran; Fabrizio Scarabino; Cristhian Clavijo; et al. (Hydrobiologia, 2013)

A Novel Human Glycoprotein ACA is an Upstream Regulator of Human Hematopoiesis - Z. A. Becker-Kojić; J. R. Ureña-Peralta; R. Saffrich; F. J. Rodriguez-Jiménez; M. P. Rubio; P. Rios; A. Romero; A. D. Ho; M. Stojković (Bulletin of Experimental Biology and Medicine, 2013)

Population dynamics of Sonoran Desert saguaro cactus ( Carnegiea gigantea ) at the Desert Laboratory (Tucson, Arizona) - Susana Rodriguez-Buritica; Helen Raichle; Trevor Birt; Robert H. Webb; Raymond M. Turner; Elizabeth A. Pierson; D. Lawrence Venable (Ecology, 2013)
The saguaro cactus ( Carnegiea gigantea ) is one of the most iconic perennials in the Sonoran Desert. The ecological importance of this species has motivated studies that explored its physiological adaptations to deserts, factors controlling its recruitment and distribution, and changes in its population density and extent over time. The population of saguaros on Tumamoc Hill (Tucson, Arizona) is one of the best studied. Saguaros on and nearby Tumamoc Hill were mapped in 1908, and in 1964 R. M. Turner and J. R. Hastings established four 250‐m wide plots within the original census area. Plots were established on the north‐, south‐, east‐, and west‐facing slopes of Tumamoc Hill, and each plot extends from the top to the base of the hill. Plots were resurveyed in 1970, 1987, 1993, and between 2010 and 2012. In this Data Paper, we present all information associated with this monitoring program, which includes digital versions of Spalding's original 1908 saguaro map as well as information regarding individual saguaros located in each of the four plots. Collected data include plant height, number of branches, and plant condition, as well as plant location. Starting in 1993, we also noted the identity and condition of plant species growing in close proximity to each saguaro. The archived data set described here contains information pertaining to >5800 saguaros. Past analyses of these data include reconstructions of regeneration patterns from observed age structures and the determination of the average height‐specific growth rates for plants on each slope. The findings from these studies have broadened our understanding of the relationship between saguaro regeneration patterns and climate. These data have also provided pivotal information regarding regional trends of saguaro populations throughout the Sonoran Desert. As a group, the Tumamoc Hill censuses constitute one of the longest spatially explicit monitoring efforts for a single species in the world. They provide an observational baseline for future comparisons relating individual growth and population demographics to rising CO 2 levels, climate change, vegetation change, or changes in other biotic or abiotic factors.

Relationship between hydraulic conductance and citrus dwarfing by the Flying Dragon rootstock (Poncirus trifoliata L. Raft var. monstruosa) - B. Martínez-Alcántara; J. Rodriguez-Gamir; M. R. Martínez-Cuenca; D. J. Iglesias; E. Primo-Millo; M. A. Forner-Giner (Trees, 2013)

Epidemiologic features of borderline ovarian tumors in California: a population-based study - Cyllene R. Morris; Lihua Liu; Anne O. Rodriguez; Rosemary D. Cress; Kurt Snipes (Cancer Causes & Control, 2013)

Virtual Treatment of Basilar Aneurysms Using Shape Memory Polymer Foam - J. M. Ortega; J. Hartman; J. N. Rodriguez; D. J. Maitland (Annals of Biomedical Engineering, 2013)

Investigations into the differential reactivity of endogenous and exogenous mercury species in coastal sediments - S. Bouchet; P. Rodriguez-Gonzalez; R. Bridou; M. Monperrus; E. Tessier; P. Anschutz; R. Guyoneaud; D. Amouroux (Environmental Science and Pollution Research, 2013)

Spatial impact of projected changes in rainfall and temperature on wheat yields in Australia - A. Potgieter; H. Meinke; A. Doherty; V. O. Sadras; G. Hammer; S. Crimp; D. Rodriguez (Climatic Change, 2013)

Testing for hybridization and assessing genetic diversity in Morelet’s crocodile (Crocodylus moreletii) populations from central Veracruz - Ricardo González-Trujillo; David Rodriguez; Alberto González-Romero; Michael R. J. Forstner; Llewellyn D. Densmore III; Víctor Hugo Reynoso (Conservation Genetics, 2012)

Zygomycosis Caused by Rhizopus microsporus and Rhizopus oryzae in Madhya Pradesh (M.P.) Central India: A Report of Two Cases - Shesh R. Nawange; S. M. Singh; J. Naidu; S. Jain; T. Nagpal; D. S. Behrani; E. Mellado; J. L. Rodriguez Tudela (Mycopathologia, 2012)

Low genetic diversity and evidence of population structure among subspecies of Nerodia harteri, a threatened water snake endemic to Texas - David Rodriguez; Michael R. J. Forstner; Dustin L. McBride; Llewellyn D. Densmore III; James R. Dixon (Conservation Genetics, 2012)

The Garzón Massif, Colombia-a new ultrahigh-temperature metamorphic complex in the Early Neoproterozoic of northern South America - U. Altenberger; D. M. Mejia Jimenez; C. Günter; G. I. Sierra Rodriguez; F. Scheffler; R. Oberhänsli (Mineralogy and Petrology, 2012)

BK virus infection in human immunodeficiency virus-infected patients - J. Ledesma; P. Muñoz; D. Garcia de Viedma; I. Cabrero; B. Loeches; P. Montilla; P. Gijon; B. Rodriguez-Sanchez; E. Bouza (European Journal of Clinical Microbiology & Infectious Diseases, 2012)

Genetic structure and linkage disequilibrium in landrace populations of barley in Sardinia - Monica Rodriguez; Domenico Rau; Donal O’Sullivan; Anthony H. D. Brown; Roberto Papa; Giovanna Attene (Theoretical and Applied Genetics, 2012)

Molecular characterization of Staphylococcus aureus from outpatients in the Caribbean reveals the presence of pandemic clones - A.-C. Uhlemann; C. Dumortier; C. Hafer; B. S. Taylor; J. Sánchez E.; C. Rodriguez-Taveras; P. Leon; R. Rojas; C. Olive; F. D. Lowy (European Journal of Clinical Microbiology & Infectious Diseases, 2012)

The Cassava Genome: Current Progress, Future Directions - Simon Prochnik; Pradeep Reddy Marri; Brian Desany; Pablo D. Rabinowicz; Chinnappa Kodira; Mohammed Mohiuddin; Fausto Rodriguez; Claude Fauquet; Joseph Tohme; Timothy Harkins; Daniel S. Rokhsar; Steve Rounsley (Tropical Plant Biology, 2012)

Non-redox-active lipoate derivates disrupt cancer cell mitochondrial metabolism and are potent anticancer agents in vivo - Zuzana Zachar; James Marecek; Claudia Maturo; Sunita Gupta; Shawn D. Stuart; Katy Howell; Alexandra Schauble; Joanna Lem; Arin Piramzadian; Sameer Karnik; King Lee; Robert Rodriguez; et al. (Journal of Molecular Medicine, 2011)

Phenotype changes inherited by crossing pyrethroid susceptible and resistant genotypes from the cattle tick Riphicephalus (Boophilus) microplus - G. Aguilar-Tipacamú; R. Rosario-Cruz; Robert J. Miller; Felix D. Guerrero; R. I. Rodriguez-Vivas; Z. García-Vázquez (Experimental and Applied Acarology, 2011)

Nucleic Acid Amplification-Based Methods for Detection of Enteric Viruses: Definition of Controls and Interpretation of Results - Martin D’Agostino; Nigel Cook; David Rodriguez-Lazaro; Saskia Rutjes (Food and Environmental Virology, 2011)

Characterization of root-nodulating bacteria associated to Prosopis farcta growing in the arid regions of Tunisia - A. Fterich; M. Mahdhi; M. A. Caviedes; E. Pajuelo; R. Rivas; I. D. Rodriguez-Llorente; M. Mars (Archives of Microbiology, 2011)

Effect of human-mediated migration and hybridization on the recovery of the American crocodile in Florida (USA) - David Rodriguez; Michael R. J. Forstner; Paul E. Moler; Joseph A. Wasilewski; Michael S. Cherkiss; Llewellyn D. Densmore III (Conservation Genetics, 2011)

Effect of the Antimicrobial Peptide Tritrpticin on the In Vitro Viability and Growth of Trichomonas vaginalis - Veronica V. Infante; Alma D. Miranda-Olvera; Luis M. De Leon-Rodriguez; Fernando Anaya-Velazquez; Mayra C. Rodriguez; Eva E. Avila (Current Microbiology, 2011)

Presence of Symbiodinium spp. in macroalgal microhabitats from the southern Great Barrier Reef - D. E. Venera-Ponton; G. Diaz-Pulido; M. Rodriguez-Lanetty; O. Hoegh-Guldberg (Coral Reefs, 2010)

Sex-specific genetic architecture of human fatness in Chinese: the SAPPHIRe Study - Y.-F. Chiu; L.-M. Chuang; H.-Y. Kao; K.-C. Shih; M.-W. Lin; W.-J. Lee; T. Quertermous; J. D. Curb; I. Chen; B. L. Rodriguez; C. A. Hsiung (Human Genetics, 2010)

Cost-efficient management of coastal aquifers via recharge with treated wastewater and desalination of brackish groundwater: application to the Akrotiri basin and aquifer, Cyprus - A. D. Koussis; E. Georgopoulou; A. Kotronarou; K. Mazi; P. Restrepo; G. Destouni; C. Prieto; J. J. Rodriguez; J. Rodriguez-Mirasol; T. Cordero; C. Ioannou; A. Georgiou; et al. (Hydrological Sciences Journal, 2010)

Cost-efficient management of coastal aquifers via recharge with treated wastewater and desalination of brackish groundwater: general framework - A. D. Koussis; E. Georgopoulou; A. Kotronarou; D. P. Lalas; P. Restrepo; G. Destouni; C. Prieto; J. J. Rodriguez; J. Rodriguez-Mirasol; T. Cordero; A. Gomez-Gotor (Hydrological Sciences Journal, 2010)

Hepatitis A Virus: State of the Art - Rosa M. Pintó; M. Isabel Costafreda; Francisco J. Pérez-Rodriguez; Lucía D’Andrea; Albert Bosch (Food and Environmental Virology, 2010)

Characterization of three sect. Caulopterae species (Baccharis-Asteraceae) inferred from morphoanatomy, polypeptide profiles and spectrophotometry data - M. V. Rodriguez; M. L. Martínez; A. A. Cortadi; A. Bandoni; D. A. Giuliano; S. J. Gattuso; M. A. Gattuso (Plant Systematics and Evolution, 2010)

Geomorphological reconstruction and morphometric modelling applied to past volcanism - A. Rodriguez-Gonzalez; J. L. Fernandez-Turiel; F. J. Perez-Torrado; D. Gimeno; M. Aulinas (International Journal of Earth Sciences, 2010)

Quantifying the limits of HANPP and carbon emissions which prolong total species well-being - Justin D. K. Bishop; Gehan A. J. Amaratunga; Cuauhtemoc Rodriguez (Environment, Development and Sustainability, 2010)

Lack of heterogeneity of HPV16 E7 sequence compared with HPV31 and HPV73 may be related to its unique carcinogenic properties - Mahboobeh Safaeian; Koenraad van Doorslaer; Mark Schiffman; Zigui Chen; Ana Cecilia Rodriguez; Rolando Herrero; Allan Hildesheim; Robert D. Burk (Archives of Virology, 2010)

One Hundred Questions of Importance to the Conservation of Global Biological Diversity - W. J. SUTHERLAND; W. M. ADAMS; R. B. ARONSON; R. AVELING; T. M. BLACKBURN; S. BROAD; G. CEBALLOS; I. M. CÔTÉ; R. M. COWLING; G. A. B. DA FONSECA; E. DINERSTEIN; P. J. FERRARO; et al. (Conservation Biology, 2009)
We identified 100 scientific questions that, if answered, would have the greatest impact on conservation practice and policy. Representatives from 21 international organizations, regional sections and working groups of the Society for Conservation Biology, and 12 academics, from all continents except Antarctica, compiled 2291 questions of relevance to conservation of biological diversity worldwide. The questions were gathered from 761 individuals through workshops, email requests, and discussions. Voting by email to short‐list questions, followed by a 2‐day workshop, was used to derive the final list of 100 questions. Most of the final questions were derived through a process of modification and combination as the workshop progressed. The questions are divided into 12 sections: ecosystem functions and services, climate change, technological change, protected areas, ecosystem management and restoration, terrestrial ecosystems, marine ecosystems, freshwater ecosystems, species management, organizational systems and processes, societal context and change, and impacts of conservation interventions. We anticipate that these questions will help identify new directions for researchers and assist funders in directing funds.

Osteomyelitis of the jaw: resistance to clindamycin in patients with prior antibiotics exposure - C. Pigrau; B. Almirante; D. Rodriguez; N. Larrosa; S. Bescos; G. Raspall; A. Pahissa (European Journal of Clinical Microbiology & Infectious Diseases, 2009)

Inhaled aminoglycosides in cancer patients with ventilator-associated Gram-negative bacterial pneumonia: safety and feasibility in the era of escalating drug resistance - D. E. Ghannam; G. H. Rodriguez; I. I. Raad; A. Safdar (European Journal of Clinical Microbiology & Infectious Diseases, 2009)

Transcriptional activity and distribution of splicing machinery elements during Hyacinthus orientalis pollen tube growth - K. Zienkiewicz; A. Zienkiewicz; M. I. Rodriguez-Garcia; D. J. Smoliński; M. Świdziński; E. Bednarska (Protoplasma, 2008)

Post-Treatment Hemodynamics of a Basilar Aneurysm and Bifurcation - J. Ortega; J. Hartman; J. Rodriguez; D. Maitland (Annals of Biomedical Engineering, 2008)

Expression of WUSCHEL in Coffea canephora causes ectopic morphogenesis and increases somatic embryogenesis - A. Arroyo-Herrera; A. Ku Gonzalez; R. Canche Moo; F. R. Quiroz-Figueroa; V. M. Loyola-Vargas; L. C. Rodriguez-Zapata; C. Burgeff D′Hondt; V. M. Suárez-Solís; E. Castaño (Plant Cell, Tissue and Organ Culture (PCTOC), 2008)

Genome-wide screen for asthma in Puerto Ricans: evidence for association with 5q23 region - Shweta Choudhry; Margaret Taub; Rui Mei; José Rodriguez-Santana; William Rodriguez-Cintron; Mark D. Shriver; Elad Ziv; Neil J. Risch; Esteban González Burchard (Human Genetics, 2008)

Characteristics of Streptococcus bovis endocarditis and its differences with Streptococcus viridans endocarditis - J. Corredoira; M. P. Alonso; A. Coira; E. Casariego; C. Arias; D. Alonso; J. Pita; A. Rodriguez; M. J. López; J. Varela (European Journal of Clinical Microbiology & Infectious Diseases, 2008)

Polymorphism in the Matrix Metalloproteinase-2 Gene Promoter is Associated with Cervical Neoplasm Risk in Mexican Women - Luz M. Baltazar-Rodriguez; Aristoteles Anaya-Ventura; Maricela Andrade-Soto; Elisa A. Monrroy-Guizar; Jose R. Bautista-Lam; Gregorio Jonguitud-Olguin; Friedman R. Cepeda-Lopez; Veronica A. Centeno-Aguilar; Nelida A. Gonzalez-Hernandez; Alejandro D. Soriano-Hernández; Mario Ramirez-Flores; Angel Lugo-Trampe; et al. (Biochemical Genetics, 2008)

Simultaneous use of the X‐ and Y‐chromosome genes SMCX , SMCY , and DBY for sex determination in the Florida manatee ( Trichechus manatus latirostris ) - Michael D. Tringali; Michelle C. Davis; Marta A. Rodriguez‐lopez; Ellen E. Bolen; Jamie G. Sullivan; Elsa M. Haubold (Marine Mammal Science, 2008)

In vitro activity of temocillin against prevalent extended-spectrum beta-lactamases producing Enterobacteriaceae from Belgian intensive care units - Y. Glupczynski; T.-D. Huang; C. Berhin; G. Claeys; M. Delmée; L. Ide; G. Ieven; D. Pierard; H. Rodriguez-Villalobos; M. Struelens; J. Vaneldere (European Journal of Clinical Microbiology & Infectious Diseases, 2007)

A marker-assisted backcross approach for developing submergence-tolerant rice cultivars - C. N. Neeraja; R. Maghirang-Rodriguez; A. Pamplona; S. Heuer; B. C. Y. Collard; E. M. Septiningsih; G. Vergara; D. Sanchez; K. Xu; A. M. Ismail; D. J. Mackill (Theoretical and Applied Genetics, 2007)

Myzus persicae is Arrested More by Blends Than by Individual Compounds Elevated in Headspace of PLRV-Infected Potato - Esther Ngumbi; Sanford D. Eigenbrode; Nilsa A. Bosque-Pérez; Hongjian Ding; Analiz Rodriguez (Journal of Chemical Ecology, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

The use of transgenic canola (Brassica napus) and plant growth-promoting bacteria to enhance plant biomass at a nickel-contaminated field site - Andrea J. Farwell; Susanne Vesely; Vincent Nero; Hilda Rodriguez; Saleh Shah; D. George Dixon; Bernard R. Glick (Plant and Soil, 2006)

Spectral and thermal sensing for nitrogen and water status in rainfed and irrigated wheat environments - G. J. Fitzgerald; D. Rodriguez; L. K. Christensen; R. Belford; V. O. Sadras; T. R. Clarke (Precision Agriculture, 2006)

Successful treatment of septic shock due to pan-resistant Acinetobacter baumannii using combined antimicrobial therapy including tigecycline - F. S. Taccone; H. Rodriguez-Villalobos; D. De Backer; V. De Moor; J. Deviere; J.-L. Vincent; F. Jacobs (European Journal of Clinical Microbiology & Infectious Diseases, 2006)

The impacts of climate change in coastal marine systems - Christopher D. G. Harley; A. Randall Hughes; Kristin M. Hultgren; Benjamin G. Miner; Cascade J. B. Sorte; Carol S. Thornber; Laura F. Rodriguez; Lars Tomanek; Susan L. Williams (Ecology Letters, 2006)
Anthropogenically induced global climate change has profound implications for marine ecosystems and the economic and social systems that depend upon them. The relationship between temperature and individual performance is reasonably well understood, and much climate‐related research has focused on potential shifts in distribution and abundance driven directly by temperature. However, recent work has revealed that both abiotic changes and biological responses in the ocean will be substantially more complex. For example, changes in ocean chemistry may be more important than changes in temperature for the performance and survival of many organisms. Ocean circulation, which drives larval transport, will also change, with important consequences for population dynamics. Furthermore, climatic impacts on one or a few ‘leverage species’ may result in sweeping community‐level changes. Finally, synergistic effects between climate and other anthropogenic variables, particularly fishing pressure, will likely exacerbate climate‐induced changes. Efforts to manage and conserve living marine systems in the face of climate change will require improvements to the existing predictive framework. Key directions for future research include identifying key demographic transitions that influence population dynamics, predicting changes in the community‐level impacts of ecologically dominant species, incorporating populations’ ability to evolve (adapt), and understanding the scales over which climate will change and living systems will respond.

Population stratification confounds genetic association studies among Latinos - Shweta Choudhry; Natasha E. Coyle; Hua Tang; Keyan Salari; Denise Lind; Suzanne L. Clark; Hui-Ju Tsai; Mariam Naqvi; Angie Phong; Ngim Ung; Henry Matallana; Pedro C. Avila; et al. (Human Genetics, 2006)

The Effects of Spatial Scale on Trophic Interactions - Johan Van de Koppel; Richard D. Bardgett; Janne Bengtsson; Claudino Rodriguez-Barrueco; Max Rietkerk; Martin J. Wassen; Volkmar Wolters (Ecosystems, 2005)

Behavioral alterations in lewis rats following two-day continuous 3-nitropropionic acid administration - J. D. Newcomb; W. D. Brown; A. I. Rodriguez; S. Garbuzova-Davis; S. Saporta; P. R. Sanberg; A. E. Willing (Neurotoxicity Research, 2005)

Characterization of Toll-like receptor 3 gene in rainbow trout (Oncorhynchus mykiss) - M. F. Rodriguez; G. D. Wiens; M. K. Purcell; Y. Palti (Immunogenetics, 2005)

Transport of symbiotic zooxanthellae in mesogleal canals of Zoanthus robustus? - Mauricio Rodriguez-Lanetty; Carol Scaramuzzi; Rosanne G. Quinnell; Anthony W. D. Larkum (Coral Reefs, 2005)

Dengue virus type 2 in Cuba, 1997: conservation of E gene sequence in isolates obtained at different times during the epidemic - R. Rodriguez-Roche; M. Alvarez; T. Gritsun; D. Rosario; S. Halstead; G. Kouri; E. A. Gould; M. G. Guzman (Archives of Virology, 2005)

Reevaluation of the earthquakes of 10 March and 19 May 1951 in southern Spain - A. Udías; D. Muñoz; E. Buforn; C. Sanz de Galdeano; C. del Fresno; I. Rodriguez (Journal of Seismology, 2005)

Transcripts of MYB-like genes respond to phosphorous and nitrogen deprivation in Arabidopsis - Christopher D. Todd; Peiyu Zeng; Alicia M. Rodriguez Huete; Mary Elizabeth Hoyos; Joe C. Polacco (Planta, 2004)

High-resolution Numerical Simulation of Flow Through a Highly Sinuous River Reach - José F. Rodriguez; Fabián A. Bombardelli; Marcelo H. García; Kelly M. Frothingham; Bruce L. Rhoads; Jorge D. Abad (Water Resources Management, 2004)

Transgenic Rice as a Vehicle for the Production of the Industrial Enzyme Transglutaminase - M.I. Claparols; L. Bassie; B. Miro; S. Del Duca; J. Rodriguez-Montesinos; P. Christou; D. Serafini-Fracassini; T. Capell (Transgenic Research, 2004)

Spatial and Seasonal Variations of Water Quality in a Mediterranean Catchment: The Llobregat River (NE Spain) - J.L. Fernández-Turiel; D. Gimeno; J.J. Rodriguez; M. Carnicero; F. Valero (Environmental Geochemistry and Health, 2003)

A comparative study of the expression of monoamine oxidase-A and -B mRNA and protein in non-CNS human tissues - S. D. Sivasubramaniam; C. C. Finch; M. J. Rodriguez; N. Mahy; E. E. Billett (Cell and Tissue Research, 2003)

Integration of soil solarization with chemical, biological and cultural control for the management of soilborne diseases of vegetables - C. Stevens; V. A. Khan; R. Rodriguez-Kabana; L. D. Ploper; P. A. Backman; D. J. Collins; J. E. Brown; M. A. Wilson; E. C. K. Igwegbe (Plant and Soil, 2003)

Comparative analysis of superfamilies of NBS-encoding disease resistance gene analogs in cultivated and wild apple species - S.-Y. Lee; J.-S. Seo; M. Rodriguez-Lanetty; D.-H. Lee (Molecular Genetics and Genomics, 2003)

Characterization of the RNA-binding activity of VP3, a major structural protein of Infectious bursal disease virus - G. Kochan; D. Gonzalez; J. F. Rodriguez (Archives of Virology, 2003)

Short‐term storage of ova of common carp and tench in extenders - O. Linhart; D. Gela; M. Rodina; M. Rodriguez Gutierrez (Journal of Fish Biology, 2001)
In a study of the effect of short‐term storage on the hatching rate of common carp Cyprinus carpio and tench Tinca tinca ova in vitro in various extenders at 21° C under aerobic conditions, the best extender for 30 min storage for common carp appeared to be Dettlaff 1. This gave the same hatching rate as controls without extender (55% v. 56%). For 60 min storage of ova, the best extenders were Dettlaff 2 (24% hatching rate) and Dettlaff 3 (30%), but hatching was significantly lower than in the control (58%). In carp ovarian artificial fluid (CAF) extender, the hatching rate of common carp ova was also high after 10 min, but decreased to 12% after 30 min. In tench, the hatching rate of ova increased after 10 min storage in Dettlaff 5 extender (44%) compared to the control (41%) without extender. However, it was significantly lower after storage in Dettlaff 1, 2, 3, 4, 5 and CAF extenders for 20, 30 and 60 min, compared to controls. Malformations (10–50%) were observed in the tench second control groups without extender after 10, 20 and 30 min storage of ova.

In vitro morphogenesis of Cucumis melo var. inodorus - Liliane C. Liborio Stipp; Beatriz M. Januzzi Mendes; Sonia M. D. Stefano Piedade; Adriana P. Martinelli Rodriguez (Plant Cell, Tissue and Organ Culture (PCTOC), 2001)

The reliability of immunohistochemistry as a prescreening method for the diagnosis of hereditary nonpolyposis colorectal cancer (HNPCC) – Results of an international collaborative study - Wolfram Müller; Lawrence J. Burgart; Ruth Krause-Paulus; Stephen N. Thibodeau; M. Almeida; T. Brocker Edmonston; C. R. Boland; C. Sutter; J. R. Jass; A. Lindblom; J. Lubinski; K. MacDermot; et al. (Familial Cancer, 2001)

Physical and chemical processes in the application of CA and/or fumigation - Cecilia V. De Dios; Maria Finesa A. Cosico; Ma. Elvira M. Martinez; D. D. Julian; I. V. Dator; R. L. Tiongson; J. van S. Graver; S. Pratt; C. Reed; Sylvia Allen; G. N. Mbata; T. W. Phillips; et al. (Phytoparasitica, 2001)

Isolation and characterization of microsatellite DNA markers in the Florida manatee ( Trichechus manatus latirostris ) and their application in selected Sirenian species - A. I. Garcia‐Rodriguez; D. Moraga‐Amador; W. Farmerie; P. Mcguire; T. L. King (Molecular Ecology, 2000)

Plant species diversity as a driver of early succession in abandoned fields: a multi-site approach - W. H. Van der Putten; S. R. Mortimer; K. Hedlund; C. Van Dijk; V. K. Brown; J. Lepä; C. Rodriguez-Barrueco; J. Roy; T. A. Diaz Len; D. Gormsen; G. W. Korthals; S. Lavorel; et al. (Oecologia, 2000)

Linkage mapping and QTL analysis in coconut (Cocos nucifera L.) - A. Herrán; L. Estioko; D. Becker; M. J. B. Rodriguez; W. Rohde; E. Ritter (Theoretical and Applied Genetics, 2000)

Transformation of floral organs with GFP in Medicago truncatula - K. Kamaté; I. D. Rodriguez-Llorente; M. Scholte; P. Durand; P. Ratet; E. Kondorosi; A. Kondorosi; T. H. Trinh (Plant Cell Reports, 2000)

A fragile X case with an amplification/deletion mosaic pattern - D. García Arocena; Y. de Diego; B.A. Oostra; R. Willemsen; M. Mirta Rodriguez (Human Genetics, 2000)

A fragile X case with an amplification/deletion mosaic pattern - D. García Arocena; Y. de Diego; B.A. Oostra; R. Willemsen; M. Mirta Rodriguez (Human Genetics, 2000)

Age structure and growth of peacock cichlids from rivers and reservoirs of Venezuela - D. B. Jepsen; K. O. Winemiller; D. C. Taphorn; D. Rodriguez Olarte (Journal of Fish Biology, 1999)
Cichla temensis collected in Venezuela attained a mean standard length of 440 mm, and C. orinocensis and C. intermedia mean lengths of 309 and 321 mm, respectively. There was little evidence of size differences between sexes. Opaque zones on otoliths corresponded to the period of peak of reproductive activity and low fish body condition ( K ). When aggregated across sites, linear estimates for growth of fish >age I were 57·5, 27·6, and 19·6 mm year 1 for C. temensis , C. orinocensis , and C. intermedia , respectively. Fish from the Cinaruco River appeared to spawn at age I, and prior to first maturation had grown 25, 21, and 23 mm month 1 , respectively, for C. temensis , C. orinocensis , and C. intermedia . There was little intersite variation in growth rates, and differences in sizes of conspecifics from different sizes were due to age differences. Cichla in captivity spawn several times per year. The present results indicate that the annual cycle or tropical wet/dry seasonality promotes reproductive seasonality in Cichla . The energetic cost of reproduction and brood defence probably constrains most individuals to one spawn per year. Conversely, populations living in relatively aseasonal reservoir environments may have several spawns per year, in which case growth zones on hard structures are difficult to interpret.

Abstracts of papers presented at an international workshop on management of soilborne pathogens sponsored by the United States-Israel binational agricultural research and development fund (bard) - R. J. Cook; J. Katan; I. Chet; J. Katan; R. Rodriguez-Kabana; C. R. Taylor; J. W. Kloepper; M. M. Satour; G. L. Lazarovits; K. L. Conn; M. Tenuta; G. Kritzman; et al. (Phytoparasitica, 1998)

Abstracts of the 6th FECS Conference 1998 Lectures - F. Sherwood Rowland; Donald R. Blake; B. R. Larsen; Anne Lindskog; Peter J. Peterson; W. Peter Williams; T. J. Wallington; M. J. Pilling; N. Carslaw; D. J. Creasey; D. E. Heard; P. Jacobs; et al. (Environmental Science and Pollution Research, 1998)

Phylogeography of the West Indian manatee ( Trichechus manatus ): how many populations and how many taxa? - A. I. GARCIA‐RODRIGUEZ; B. W. BOWEN; D. DOMNING; A. A. MIGNUCCI‐GIANNONI; M. MARMONTEL; R. A. MONTOYA‐OSPINA; B. MORALES‐VELA; M. RUDIN; R. K. BONDE; P. M. McGUIRE (Molecular Ecology, 1998)
To resolve the population genetic structure and phylogeography of the West Indian manatee ( Trichechus manatus ), mitochondrial (mt) DNA control region sequences were compared among eight locations across the western Atlantic region. Fifteen haplotypes were identified among 86 individuals from Florida, Puerto Rico, the Dominican Republic, Mexico, Colombia, Venezuela, Guyana and Brazil. Despite the manatee’s ability to move thousands of kilometres along continental margins, strong population separations between most locations were demonstrated with significant haplotype frequency shifts. These findings are consistent with tagging studies which indicate that stretches of open water and unsuitable coastal habitats constitute substantial barriers to gene flow and colonization. Low levels of genetic diversity within Florida and Brazilian samples might be explained by recent colonization into high latitudes or bottleneck effects. Three distinctive mtDNA lineages were observed in an intraspecific phylogeny of T. manatus , corresponding approximately to: (i) Florida and the West Indies; (ii) the Gulf of Mexico to the Caribbean rivers of South America; and (iii) the northeast Atlantic coast of South America. These lineages, which are not concordant with previous subspecies designations, are separated by sequence divergence estimates of d = 0.04–0.07, approximately the same level of divergence observed between T. manatus and the Amazonian manatee ( T. inunguis , n = 16). Three individuals from Guyana, identified as T. manatus , had mtDNA haplotypes which are affiliated with the endemic Amazon form T. inunguis . The three primary T. manatus lineages and the T. inunguis lineage may represent relatively deep phylogeographic partitions which have been bridged recently due to changes in habitat availability (after the Wisconsin glacial period, 10 000 BP ), natural colonization, and human‐mediated transplantation.

Effects of ? 2 -microglobulin mutations on the alpha-1 helical region of H2-L d - Carla S. Schultz; Rafael A. Rodriguez; Eleanor A. Chew; M. C. Nieto; Christian Dimaano; Fung-Mee Li; Marjorie D. Santos (Immunogenetics, 1998)

Letters - Timothy D. Male; Reed F. Noss; Timothy M. Crowe; Jon Paul Rodriguez; Gary K. Meffe (Conservation Biology, 1998)

Neurological and functional effects of short-term exposure to hand-arm vibration - J. Malchaire; L. S. Rodriguez Diaz; A. Piette; F. Gonçalves Amaral; D. de Schaetzen (International Archives of Occupational and Environmental Health, 1998)

Abstracts of presentations on plant protection issues at the xth international congress of virology - E. Ramirez; A. Hernádez; E. Ham; B. L. Barrón; S. W. Ding; W. X. Li; B. J. Shi; R. H. Symons; Q. Li; K. H. Ryu; P. Palukaitis; I. B. Kaplan; et al. (Phytoparasitica, 1997)

Redox modulation of the response of NADH oxidase activity of rat liver plasma membranes to cyclic AMP plus ATP - D. James Morré; Juan Carlos Rodriguez-Aguilera; Placido Navas; Dorothy M. Morré (Molecular and Cellular Biochemistry, 1997)

Reproductive Toxicology of 3,3',4,4'-Tetrachlorobiphenyl in Mice - J. Rodriguez; S. D. Kholkute; W. R. Dukelow (Bulletin of Environmental Contamination and Toxicology, 1997)

Changes in carbon isotope discrimination in grain cereals from different regions of the western Mediterranean Basin during the past seven millennia. Palaeoenvironmental evidence of a differential change in aridity during the late Holocene - J.L. ARAUS; A. FEBRERO; R. BUXO; M.D. CAMALICH; D. MARTIN; F. MOLINA; M.O. RODRIGUEZ‐ARIZA; I. ROMAGOSA (Global Change Biology, 1997)
Carbon isotope discrimination (Δ) was determined for kernels of six‐row barley and durum wheat cultivated in the western Mediterranean basin during the last seven millennia. Samples came from different archaeological sites in Catalonia (north‐east Spain) and in the south‐east of Spain (mainly eastern Andalusia). Samples from the present were also analysed. Mean values of Δ for barley and durum wheat grains decreased slightly from Neolithic (7000–5000 BP) to Chalcolithic‐Bronze (5000–3000 BP) and Iron ages (3000–2200 BP) both in Catalonia and in south‐east (SE) Spain. Values were consistently lower in SE Spain than in Catalonia throughout these five millennia, which suggests that Catalonia was less arid than SE Spain in this period. Within a given region, current discrimination values for kernels of the same cereal species cultivated under rainfed conditions were lower than those of archaeological grains, which implies more arid conditions at present. Furthermore, an empirical relationship between Δ of mature kernels and total precipitation (plus irrigation where applicable) during grain filling ( r 2 = 0.73, N = 25) was established for barley, currently cultivated at different locations in the western Mediterranean basin in Spain. The resulting relationship was applied to the Δ data for barley kernels from 10 archaeological sites in Catalonia and 10 sites in SE Spain, to estimate the precipitation during grain filling at the time the kernels were produced. For both regions, current climatic conditions are consistently more arid than those inferred for the Neolithic, Bronze and Iron ages. In addition, although Catalonia was estimated to have had consistently wetter conditions (about 20% more precipitation) than SE Spain throughout these millennia, differences in precipitation between these two regions have recently increased, with 79% more precipitation in Catalonia. Results indicate a more rapid increase in aridity in SE Spain than in Catalonia, probably produced during the last few centuries, and due to anthropogenic causes.

Screening tuber-bearingSolanum species for resistance toHelminthosporium solani - D. A. Rodriguez; G. A. Secor; N. C. Gudmestad; K. Grafton (American Journal of Potato Research, 1995)

Human acetylator genotype: Relationship to colorectal cancer incidence and arylamine N-acetyltransferase expression in colon cytosol - Jose W. Rodriguez; Ward G. Kirlin; Ronald J. Ferguson; Mark A. Doll; Kevin Gray; Timothy D. Rustan; Mark E. Lee; Katherine Kemp; Paul Urso; David W. Hein (Archives of Toxicology, 1993)

Lipopolysaccharides of Thiobacillus species containing lipid A with 2,3-diamino-2,3-dideoxyglucose - A. Yokota; M. Rodriguez; Y. Yamada; K. Imai; D. Borowiak; H. Mayer (Archives of Microbiology, 1987)

Degradation of carbaryl by soil microorganisms - Lorraine D. Rodriguez; H. Wyman Dorough (Archives of Environmental Contamination and Toxicology, 1977)

Clinical, virological, and pathological features of herpesvirus SA8 infection in conventional and gnotobiotic infant baboons(Papio cynocephalus) - J. W. Eichberg; B. McCullough; S. S. Kalter; D. E. Thor; A. R. Rodriguez (Archives of Virology, 1976)

s 60th annual PAA meeting (Part II) - J. Landeo; P. R. Rowe; M. Mayer de Scurrah; M. T. Jackson; P. R. Rowe; J. G. Hawkes; P. Jatala; H. A. Mendoza; F. L. Haynes; G. C. C. Tai; H. Dejong; N. S. Wright; et al. (American Journal of Potato Research, 1976)